Porous support-zeolite membrane composite, method for producing purified component, and method for producing purified organic compound

By controlling the permeation rate and SiO2/Al2O3 molar ratio of the porous support-zeolite membrane composite, the crystal orientation and membrane thickness of the zeolite membrane are optimized, solving the problems of insufficient separation selectivity and difficulty in achieving acid resistance in the existing zeolite membrane composite, and realizing a zeolite membrane composite with high separation performance and acid resistance.

CN120882476APending Publication Date: 2025-10-31MITSUBISHI CHEM CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202480022736.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-03-31
Filing Date
2024-04-01
Publication Date
2025-10-31

AI Technical Summary

Technical Problem

Existing zeolite membrane composites lack sufficient separation selectivity in the separation of aqueous organic compounds, and it is difficult to balance acid resistance and durability.

Method used

By controlling the CF4 permeation rate, SF6 permeation rate, and SiO2/Al2O3 molar ratio of the zeolite membrane in the porous support-zeolite membrane composite, the crystal orientation and membrane thickness of the zeolite membrane are optimized to form a composite with high separation performance and acid resistance.

Benefits of technology

It achieves high separation performance and excellent acid resistance, and is suitable for the separation of lower alcohols and electrophilic molecules, thus improving separation efficiency and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The purpose of one embodiment of the present invention is to achieve a porous support-zeolite membrane composite having excellent separation performance. A porous support-zeolite membrane composite according to one embodiment of the present invention has a CF4 permeation amount of 5.0 * 10 <-9 > mol / (m < 2 >. S. Pa) or less, and the zeolite membrane has a membrane thickness of 15 [mu] m or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to porous support-zeolite membrane composites, methods for manufacturing purified components, and methods for manufacturing purified organic compounds. Background Technology

[0002] To separate water and concentrate organic compounds from aqueous organic compounds that are mixtures of water and organic solvents, membrane separation, distillation, azeotropic distillation, solvent extraction / distillation, and separation methods using adsorption materials can be used. Among these, membrane separation using zeolite membranes offers advantages over other methods, including lower energy consumption and a wider range of applicable separation and concentration targets, as well as a wider temperature range compared to membrane separation using polymer membranes. Furthermore, in the separation of carbon dioxide and methane mixtures, and the concentration of methane, separation methods based on membrane separation, adsorption separation, absorption separation, distillation, and cryogenic separation can be used. In gas separation, membrane separation using zeolite membranes offers energy savings compared to other methods and a wider range of applications compared to polymer membranes.

[0003] In methods for separating mixtures of gases or liquids containing organic matter, there are known concentration methods that utilize membrane separation using membranes made of inorganic materials such as zeolite membranes. Zeolite membranes are typically used in these separation methods as zeolite membrane composites in which the zeolite membrane is formed on a porous support. For such zeolite membrane composites, there are known CHA-type zeolite separation membranes (e.g., Patent Document 1) with high intensity of specific crystal orientations defined by X-ray diffraction (XRD) patterns, and zeolite separation membranes (e.g., Patent Document 2) with high uniformity of SAR (silica / alumina ratio) in the thickness direction.

[0004] Patent document 1 describes an inorganic porous support-zeolite membrane composite, wherein the inorganic porous support comprises a ceramic sintered body, and a CHA-type zeolite crystal layer as a zeolite membrane is present on the surface of the inorganic porous support.

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: International Publication No. 2010 / 098473

[0008] Patent Document 2: International Publication No. 2015 / 159986 Summary of the Invention

[0009] Problems solved by the invention

[0010] Although the technology described in Patent Document 1 has high selectivity in the membrane separation of aqueous organic compounds, there is still room for further improvement in selectivity.

[0011] One of the objectives of this invention is to achieve a porous support-zeolite membrane composite with excellent separation performance.

[0012] Furthermore, the zeolite membrane composite described in Patent Document 1 can achieve both sufficient throughput and separation performance in separation and concentration based on inorganic material separation membranes. The zeolite membrane composite described in Patent Document 2 exhibits excellent acid and water resistance and can possess sufficient permeation flux. Therefore, it is suitable for the separation of lower alcohols or substances such as electrophilic molecules that react with the acidic sites of zeolite.

[0013] For zeolite membrane composites, both high separation properties and durability such as acid resistance are required. However, achieving zeolite membranes with the desired properties is usually not achievable through a simple combination of technologies, and is therefore practically difficult.

[0014] One objective of this invention is to achieve an inorganic porous support-zeolite membrane composite with excellent separation properties and acid resistance.

[0015] Problem Solving Methods

[0016] In order to solve the above-mentioned problems, the main idea of ​​the present invention is as follows.

[0017] Method 1: A porous support-zeolite membrane composite, wherein,

[0018] The CF4 permeability of the porous support-zeolite membrane composite is 5.0 × 10⁻⁶. -9 mol / (m 2 The thickness of the zeolite membrane is 15 μm or less (≤ s·Pa).

[0019] Method 2: A porous support-zeolite membrane composite, comprising a porous support and a zeolite membrane formed on the porous support, wherein,

[0020] The SF6 permeability of the porous support-zeolite membrane composite is 4.5 × 10⁻⁶. -8 mol·μm / (m 2 Below ·s·Pa),

[0021] The surface SiO2 / Al2O3 molar ratio of the zeolite film is 25 or higher.

[0022] Method 3: A porous support-zeolite membrane composite, comprising a porous support and a zeolite membrane formed on the porous support, wherein,

[0023] The CF4 permeation of the porous support-zeolite membrane composite is 1.0 × 10⁻⁶. -9 mol / (m 2 ·s·Pa) and below.

[0024] Method 4: The porous support-zeolite membrane composite according to any one of methods 1 to 3, wherein,

[0025] When X-rays are irradiated onto the surface of the zeolite membrane at the minimum incident angle that allows X-rays to penetrate the membrane, the integrated intensity of the peak near 2θ=9.6° in the X-ray diffraction pattern is more than 6.0 times that of the peak near 2θ=20.8°.

[0026] Method 5: The porous support-zeolite membrane composite according to Method 1 or 3, wherein,

[0027] The surface SiO2 / Al2O3 molar ratio of the zeolite membrane is 25 or higher.

[0028] Method 6: The porous support-zeolite membrane composite according to Method 2 or 3, wherein,

[0029] The thickness of the zeolite membrane is less than 15 μm.

[0030] Method 7: A porous support-zeolite membrane composite according to any one of methods 1 to 6, wherein,

[0031] In the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays, the peak intensity I near 2θ = 17.9° is... 111 The peak intensity I is near 2θ = 20.8°. 20-1 More than 0.3 times and less than 1.0 times.

[0032] Method 8: A porous support-zeolite membrane composite according to any one of methods 1 to 7, wherein,

[0033] The peak intensity I near 2θ = 9.6° in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays. 100 The peak intensity I relative to 2θ = 20.8° 20-1 The ratio of I 100 / I 20-1 It is more than 0.7 times.

[0034] Method 9: A porous support-zeolite membrane composite according to any one of methods 1 to 8, wherein,

[0035] The ratio C / D of the SiO2 / Al2O3 molar ratio C on the surface of the zeolite film relative to the SiO2 / Al2O3 molar ratio D in the central part of the zeolite film along the film thickness direction is less than 1.5.

[0036] Method 10: A porous support-zeolite membrane composite according to any one of methods 1 to 9, wherein,

[0037] The thickness of the zeolite membrane is 3 μm or more.

[0038] Method 11: The porous support-zeolite membrane composite according to any one of methods 1 to 10, wherein,

[0039] The minimum thickness of the zeolite membrane is 5 μm or more.

[0040] Method 12: The porous support-zeolite membrane composite according to any one of methods 1 to 11, wherein,

[0041] The zeolite membrane is composed of CHA-type zeolite.

[0042] Method 13: A method for manufacturing a purified component, the method comprising:

[0043] The mixture of a first component of the zeolite membrane and a second component that does not permeate the zeolite membrane in any one of the permeation methods 1 to 12 is brought into contact with the porous support-zeolite membrane composite to obtain one or both of a first purified component that permeates the zeolite membrane and a second purified component that does not permeate the zeolite membrane.

[0044] Method 14: The method for manufacturing the purified component according to Method 13, wherein,

[0045] Both the first component and the second component are liquids.

[0046] Method 15: A method for manufacturing the purified component according to Method 13, wherein,

[0047] Both the first component and the second component are gases.

[0048] Method 16: The method for manufacturing the purified component according to Method 13, wherein,

[0049] One of the first component and the second component is water, and the other is a water-soluble organic compound.

[0050] Method 17: A method for manufacturing the purified component according to Method 13, wherein,

[0051] One of the first component and the second component is water, and the other contains an acid.

[0052] Method 18: A method for producing purified organic compounds, comprising using a porous support-zeolite membrane composite having a porous support and a zeolite membrane formed on the porous support to obtain purified organic compounds from a mixture containing organic compounds, wherein...

[0053] The porous support-zeolite membrane composite is any one of the porous support-zeolite membrane composites described in methods 1 to 3.

[0054] The effects of the invention

[0055] According to one aspect of the present invention, a porous support-zeolite membrane composite with excellent separation performance can be achieved.

[0056] In addition, according to one aspect of the present invention, an inorganic porous support-zeolite membrane composite with excellent separation characteristics and acid resistance can be realized. Attached Figure Description

[0057] Figure 1 This is a diagram illustrating a portion of the zeolite membrane in the thickness direction of the present invention.

[0058] Figure 2 This is a schematic diagram illustrating the configuration of the apparatus used in the gas permeation test in the embodiment.

[0059] Figure 3 This is a schematic diagram illustrating the configuration of the apparatus used in the pervaporation method in the embodiments.

[0060] Figure 4 This is a diagram showing the X-ray diffraction pattern of membrane complex 1.

[0061] Figure 5 This is a diagram showing the X-ray diffraction pattern of the zeolite membrane of membrane complex 2.

[0062] Figure 6 This is a diagram showing the X-ray diffraction pattern of the zeolite membrane of membrane complex 3.

[0063] Figure 7 This is a schematic diagram illustrating the configuration of a pervaporation measurement apparatus.

[0064] Figure 8 This is a scanning electron microscope image showing the surface of the zeolite membrane of membrane composite 1 before acid impregnation.

[0065] Figure 9 This is a scanning electron microscope image showing the surface of the zeolite membrane of membrane composite 1 after acid impregnation.

[0066] Figure 10 This is a scanning electron microscope image showing the surface of the zeolite membrane of membrane complex 2 before acid impregnation.

[0067] Figure 11 This is a scanning electron microscope image showing the surface of the zeolite membrane of membrane composite 2 after acid impregnation.

[0068] Symbol Explanation

[0069] 1. Mixer

[0070] 2. Hot bath

[0071] 3. Stirring

[0072] 4. Separated liquid

[0073] 5. Zeolite membrane composite

[0074] 6. Pirani type vacuum gauge

[0075] 7. Through liquid trap

[0076] 8 Cold trap

[0077] 9. Vacuum pump

[0078] 10, 21 Membrane complex

[0079] 11. Zeolite membrane

[0080] 11A Surface Section

[0081] 11B Central Division

[0082] 11C bottom

[0083] 12 Porous supports (inorganic porous supports)

[0084] 22 Pressure Vessels

[0085] 23 End pins

[0086] 24 Connecting parts

[0087] 25 Pressure gauge

[0088] 26 Back pressure valve

[0089] 27. Gas supply

[0090] 28. Through gas

[0091] 29. Exhaust gas

[0092] 30 piping

[0093] 31 Membrane Module

[0094] 32 Vacuum Pump

[0095] 33 Glass trap

[0096] 34 Circulation Pump

[0097] 35A and 35B temperature control units

[0098] 36 Solvent Tanks

[0099] V1, V2, V3, V4, V5 valves Detailed Implementation

[0100] [Implementation Method 1]

[0101] Hereinafter, one embodiment 1 of the present invention will be described in detail.

[0102] To address the aforementioned problems, the inventors conducted repeated and in-depth research. As a result, the inventors discovered that porous support-zeolite membrane composites, where the permeation coefficient (CF4 permeation, SF6 permeation, or the product of CF4 permeation or SF6 permeation and membrane thickness) as indicators of the amount of defects present in the zeolite membrane, exhibit excellent separation performance within a specific range, thus completing the present invention.

[0103] The embodiments of the present invention will now be described in detail. However, the description of the constituent elements described below is only one example of an embodiment of the present invention, and the present invention is not limited to these contents. Various modifications can be made within the scope of its spirit. In addition, other measuring devices capable of performing equivalent measurements and processing may be used instead of the measuring device described in this specification.

[0104] [Porous Support-Zeolite Membrane Composite]

[0105] One embodiment of the present invention is a porous support-zeolite membrane composite comprising a porous support and a zeolite membrane formed on the porous support, wherein the CF4 permeation or SF6 permeation of the porous support-zeolite membrane composite is 5.0 × 10⁻⁶. -9 mol / (m 2 ·s·Pa) and below.

[0106] The permeability as CF4 or SF6 is 5.0 × 10⁻⁶. -9 mol / (m 2 For alternatives below 1000 s·Pa, the transmittance of CF4 or SF6 can be 4.5 × 10⁻⁶. -8 mol·μm / (m 2 ·s·Pa) and below.

[0107] In addition, the permeation amount as CF4 or SF6 is 5.0 × 10⁻⁶. -9mol / (m 2 For substitutions below ·s·Pa, the permeation capacity of CF4 or SF6 can be 1.0×10⁻⁶. -9 mol / (m 2 ·s·Pa) and below.

[0108] According to one aspect of the porous support-zeolite membrane composite of the present invention, a porous support-zeolite membrane composite with excellent separation performance can be achieved. The porous support-zeolite membrane composite of the present invention exhibits superior separation performance compared to the prior art, particularly in the separation and concentration of aqueous organic mixtures with low water content (e.g., less than 5% by mass).

[0109] In this specification, the "porous support-zeolite membrane composite" of one aspect of the present invention is sometimes simply referred to as "membrane composite".

[0110] The membrane composite has a porous support and a zeolite membrane formed on the porous support. The following describes non-limiting features of the porous support and the zeolite membrane.

[0111] (Porous support)

[0112] In one embodiment of the invention, the porous support is a component for supporting a zeolite film on its surface. Alternatively, the porous support can also be a component for allowing fluids, such as aqueous organic mixtures that are mixtures of water and organic compounds, to permeate through its porous structure.

[0113] As a porous support, any material with an inorganic porous structure that possesses chemical stability, such as the ability of zeolite to crystallize into a film, can be used (inorganic porous support). Examples of porous supports include: sintered ceramic bodies such as silica, α-alumina, γ-alumina, mullite, zirconium oxide, titanium dioxide, yttrium oxide, silicon nitride, or silicon carbide (ceramic supports); sintered metals such as iron, bronze, and stainless steel; other porous supports such as glass and carbon-formed bodies; and any combination thereof; etc.

[0114] Among porous supports, inorganic porous supports comprising a ceramic sintered body obtained by sintering ceramics are preferred, wherein the ceramic is a solid material whose basic components or which is mostly composed of inorganic non-metallic substances. For such inorganic porous supports, zeolizing a portion of the inorganic porous support during the synthesis of the zeolite membrane can improve the interfacial adhesion between the inorganic porous support and the zeolite membrane, and is therefore preferred.

[0115] Examples of ceramic sintered bodies include those containing at least one of silica, α-alumina, γ-alumina, mullite, zirconium oxide, titanium dioxide, yttrium oxide, silicon nitride, and silicon carbide. Among these ceramic sintered bodies, those containing at least one of α-alumina, γ-alumina, silica, and mullite are preferred. Of particular, α-alumina is most preferred from the viewpoint of chemical stability and low cost. Such ceramic sintered bodies readily undergo localized zeolization, thus strengthening the bond between the porous support and the zeolite, and easily forming a dense membrane composite with high separation performance.

[0116] The shape of the porous support is not particularly limited as long as it can effectively separate mixtures of liquids or gases. Examples of porous support shapes include: flat plates; tubular; columnar; cylindrical; honeycomb structures with multiple cylindrical, prismatic, or cylindrical pores; and monoliths; etc. From the viewpoint of increasing the effective area, cylindrical, honeycomb, or monolithic shapes are preferred, and cylindrical shapes are more preferred.

[0117] In one aspect of the invention, a membrane composite is formed by forming a zeolite membrane on the surface of a porous support. The surface of the porous support on which the zeolite membrane is formed can be any surface, or multiple surfaces, depending on the shape of the porous support. For example, when the porous support is cylindrical, the surface on which the zeolite membrane is formed can be either the outer surface or the inner surface of the cylinder, or both surfaces. From the viewpoint of membrane permeation resistance and ease of synthesis, it is more preferable to form it on the outer surface.

[0118] The average thickness (wall thickness) of the porous support is typically 0.1 mm or more, preferably 0.3 mm or more, and more preferably 0.5 mm or more. When the average thickness of the porous support is within this range, the membrane composite can exhibit high mechanical strength. The average thickness of the porous support is typically 7 mm or less, preferably 5 mm or less, and more preferably 3 mm or less. When the average thickness of the porous support is within this range, the diffusion of the material permeating the membrane composite is promoted, and the permeation velocity is increased.

[0119] The porosity of the porous support is typically 20% or more, preferably 25% or more, and more preferably 30% or more. When the porosity of the porous support is within this range, the diffusion of the material permeating the membrane composite is promoted, and the permeation velocity is increased. The porosity of the porous support is typically 70% or less, preferably 60% or less, and more preferably 50% or less. When the porosity of the porous support is within this range, the membrane composite can possess high mechanical strength.

[0120] [Zeolite membrane]

[0121] In one aspect of the invention, a zeolite membrane is a component used in the separation and concentration of a fluid comprising a mixture of multiple components to separate a portion of the components contained in the mixture and to concentrate a portion of the components by allowing a portion of the components to pass through and preventing a portion of the components from passing through.

[0122] Zeolite films form on the surface of a porous support in the form of zeolite film crystals. The zeolite film crystals can form a uniform and single layer, or a non-uniform layer composed of multiple zeolite crystal particles with particle interfaces within the film.

[0123] In zeolite membranes, the main part exists on the surface of the porous support, and a portion of it can also enter the surface layer of the porous support.

[0124] Zeolite films contain zeolite as their component and are formed by the crystallization of zeolite into a film-like structure. Besides zeolite, zeolite films may also contain, as needed: inorganic binders such as silica and alumina, organic compounds such as polymers, materials containing Si atoms (silylating agents) or their reaction products to modify the zeolite surface, etc. Additionally, zeolite films may contain some amorphous components. Furthermore, zeolite films may include surface-applied metals.

[0125] <sar>

[0126] The SiO2 / Al2O3 molar ratio (hereinafter also referred to as "SAR") in the central part of the zeolite membrane is typically 5 or more, preferably 10 or more, more preferably 15 or more, even more preferably 18 or more, particularly preferably 20 or more, even more preferably 25 or more, typically 70 or less, preferably 60 or less, and more preferably 50 or less. By making the SiO2 / Al2O3 molar ratio of the zeolite membrane at or above the aforementioned lower limit value, the acid resistance of the zeolite membrane becomes good. By making the SiO2 / Al2O3 molar ratio of the zeolite membrane at or below the aforementioned upper limit value, the hydrophilicity of the zeolite membrane becomes good, and the permeability of water and carbon dioxide becomes good.

[0127] The SiO2 / Al2O3 molar ratio (hereinafter also referred to as "surface SAR") measured on the surface of the zeolite membrane is typically 5 or more, preferably 10 or more, more preferably 15 or more, further preferably 18 or more, particularly preferably 20 or more, even more preferably 25 or more, typically 70 or less, preferably 60 or less, and more preferably 50 or less. By making the SiO2 / Al2O3 molar ratio of the zeolite membrane above or below the aforementioned lower limit, the acid resistance of the zeolite membrane becomes good. By making the SiO2 / Al2O3 molar ratio of the zeolite membrane below or below the aforementioned upper limit, the hydrophilicity of the zeolite membrane becomes good, and the permeability of water and carbon dioxide becomes good.

[0128] In one aspect of the membrane composite of the present invention, the SiO2 / Al2O3 molar ratio of the zeolite membrane can be in the lower range for zeolites, generally referred to as high-silica zeolites, with a SiO2 / Al2O3 molar ratio of 5 or higher. It is generally believed that if the SiO2 / Al2O3 molar ratio is low, the crystallization rate is fast, and the zeolite membrane tends to grow in random directions, thus making it prone to defects. However, the zeolite membrane of one aspect of the present invention exhibits reduced defects even with a low SiO2 / Al2O3 molar ratio, as indicated by, for example, the permeation of CF4, the permeation of SF6, or the permeation coefficient of CF4 or SF6, which are indicators of the amount of defects. Furthermore, by reducing defects, the amount of defects allowing organic compounds to permeate is reduced. However, the pores of zeolites with a low SiO2 / Al2O3 molar ratio have high hydrophilicity, allowing H2O molecules to easily pass through them. Therefore, the membrane composite of one aspect of the present invention exhibits excellent separation performance.

[0129] The permeability of SF6 or CF4 in the porous support-zeolite membrane composite is 4.5 × 10⁻⁶. -8 mol·μm / (m 2 When the SiO2 / Al2O3 molar ratio on the surface of the zeolite membrane is above 25 (below ·s·Pa), it can particularly achieve both good permeability and separation performance.

[0130] The SiO2 / Al2O3 molar ratio of the zeolite film described in this specification can be determined using scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX). In SEM-EDX, the accelerating voltage of the electron beam is set to approximately 6 kV. Through this measurement, the SiO2 / Al2O3 molar ratio of the zeolite film can be determined.

[0131] Furthermore, in this specification, when only the "SiO2 / Al2O3 molar ratio of the zeolite film" is mentioned, this description refers to the SiO2 / Al2O3 molar ratio of the central portion of the zeolite film. The "central portion of the zeolite film" will be explained in Embodiment 2.

[0132] <Skeleton Structure>

[0133] The zeolite constituting the zeolite film preferably has a microporous structure with oxygen 12-membered rings or less, more preferably with oxygen 10-membered rings or less, even more preferably with oxygen 8-membered rings or less, and particularly preferably with oxygen 6- to 8-membered rings. In this specification, the value of 'n' in "oxygen n-membered ring" represents the number of oxygen atoms in the micropore formed by oxygen forming the zeolite framework and T elements (elements other than oxygen constituting the framework). For example, in the case of micropores containing both oxygen 12-membered and 8-membered rings, such as in MOR-type zeolites, this zeolite is considered a zeolite with oxygen 12-membered rings.

[0134] Examples of zeolites with a fine porous structure containing 12 or fewer oxygen rings include: AEI, AEL, AFI, AFG, AFX, ANA, ATO, BEA, BRE, CAS, CDO, CHA, CON, DDR, DOH, EAB, EPI, ERI, ESV, EUO, FAR, FAU, FER, FRA, HEU, GIS, GIU, GME, GOO, ITE, KFI, LEV, LIO, LOS, LTA, LTL, LTN, MAR, MEP, MER, MEL, MON, MOR, MSO, MTF, MTN, MTW, MWF, MWW, NON, NES, OFF, PAU, PHI, RHO, RTE, RTH, RUT, SGT, SOD, STI, STT, TOL, TON, TSC, UFI, VNI, WEI, YUG, etc.

[0135] Examples of zeolites with a fine porous structure containing oxygen 10-membered rings or less include: AEI, AEL, AFG, AFX, ANA, BRE, CAS, CDO, CHA, DDR, DOH, EAB, EPI, ERI, ESV, EUO, FAR, FER, FRA, HEU, GIS, GIU, GOO, ITE, KFI, LEV, LIO, LOS, LTA, LTN, MAR, MEP, MER, MEL, MON, MSO, MTF, MTN, MWF, MWW, NON, NES, PAU, PHI, RHO, RTE, RTH, RUT, SGT, SOD, STI, STT, TOL, TON, TSC, UFI, VNI, WEI, YUG, etc.

[0136] Examples of zeolites with a fine porous structure containing oxygen 8-membered rings or less include: AEI, AFG, AFX, ANA, BRE, CAS, CDO, CHA, DDR, DOH, EAB, EPI, ERI, ESV, FAR, FRA, GIS, GIU, GOO, ITE, KFI, LEV, LIO, LOS, LTA, LTN, MAR, MEP, MER, MON, MSO, MTF, MTN, MWF, NON, PAU, PHI, RHO, RTE, RTH, RUT, SGT, SOD, TOL, TSC, UFI, VNI, YUG, etc.

[0137] Examples of zeolites with oxygen 6-8 membered ring structures include: AEI, AFG, AFX, ANA, CHA, DDR, EAB, ERI, ESV, FAR, FRA, GIS, ITE, KFI, LEV, LIO, LOS, LTA, LTN, MAR, MWF, PAU, RHO, RTH, SOD, TOL, UFI, etc.

[0138] In the membrane complex, from the viewpoint of adjusting the zeolite pore diameter to allow carbon dioxide to easily diffuse within the zeolite pores and to prevent hydrocarbons from easily entering the pores, a structure with an oxygen 6-8 membered ring structure and three-dimensionally connected pores is preferred. That is, the preferred structures of the main zeolite constituting the zeolite membrane are AEI, AFG, AFX, CHA, DDR, EAB, ERI, ESV, FAR, FRA, GIS, ITE, KFI, LEV, LIO, LOS, LTN, MAR, PAU, RHO, RTH, SOD, TOL, and UFI; more preferred structures are AEI, AFX, CHA, DDR, ERI, KFI, LEV, PAU, RHO, RTH, and UFI; further preferred structures are AFX, CHA, DDR, RHO, and MWF; particularly preferred structures are AFX, CHA, DDR, or RHO; and the most preferred structure is CHA. In other words, the most preferred zeolite membrane is composed of CHA-type zeolite.

[0139] In this specification, "zeolite membrane composed of CHA-type zeolite" means that the zeolite membrane may contain components other than zeolite, including zeolites other than CHA zeolite. Typically, the main component of the zeolite membrane is CHA-type zeolite. For example, "zeolite membrane composed of CHA-type zeolite" means that the CHA-type zeolite content in the zeolite membrane is typically 90% by mass or more, preferably 95% by mass or more. The CHA-type zeolite content in the zeolite membrane can be determined by the ratio of the integral values ​​of the XRD peaks.

[0140] The microporous structure of zeolite can be appropriately selected from the microporous structures specifically listed above, depending on the application of the membrane complex.

[0141] In this specification, the structure of zeolite is represented by the code for the structure of zeolite as defined by the International Zeolite Association (IZA). Furthermore, the attribution of X-ray diffraction patterns is based on the COLLECTION OF SIMULATED XRD POWDER PATTERNS FOR ZEOLITE Third Revised Edition 2001.

[0142] <Orientation Characteristics>

[0143] When the zeolite film is composed of CHA-type zeolite, the peak intensity I near 2θ = 17.9° is observed in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays. 111 The peak intensity I is typically around 2θ = 20.8°. 20-1 The peak intensity I is at least 0.30 times, preferably at least 0.35 times, more preferably at least 0.40 times, and typically less than 1.00 times, preferably less than 0.80 times, more preferably less than 0.70 times. 111 When the above range is met, defects in the zeolite membrane caused by thermal expansion during the manufacturing process of the membrane composite, such as during firing, are further reduced, resulting in superior separation performance of the membrane composite. It should be noted that in this specification, "nearby" refers to a range of ±0.6° centered on the value described above.

[0144] When the zeolite film is composed of CHA-type zeolite, the peak intensity I at 2θ = 9.6° ± 0.6° is obtained in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays. 100 The peak intensity I is typically 2θ = 20.8° ± 0.6°. 20-1 The peak intensity is 0.80 times or more, preferably 0.90 times or more, more preferably 1.00 times or more, particularly preferably 1.10 times or more, typically less than 4.00 times, preferably less than 3.90 times, more preferably less than 3.70 times, and particularly preferably less than 3.50 times. 100 When the above range is met, defects in the zeolite membrane caused by thermal expansion during the manufacturing of the membrane composite, such as during firing, are reduced, and therefore the separation performance of the membrane composite is better.

[0145] When the zeolite film is composed of CHA-type zeolite, the peak intensity I at 2θ = 9.6° ± 0.6° is obtained in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays. 100 The peak intensity I is typically 2θ = 17.9° ± 0.6°. 111 The peak intensity I is 0.70 times or more, preferably 1.00 times or more, more preferably 1.50 times or more, typically less than 10.0 times, preferably less than 9.50 times, and more preferably less than 9.00 times. 111 When the above range is met, defects generated in the zeolite membrane due to thermal expansion during the manufacturing of the membrane composite, such as during firing, are reduced, thus resulting in superior separation performance of the membrane composite. When the membrane thickness is 5 μm or more, it is preferably 5.00 times or less, more preferably 4.50 times or less, and even more preferably 4.00 times or less.

[0146] In this embodiment, when the zeolite film is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays, the integrated intensity near 2θ=17.9° is typically 0.20 times or more, preferably 0.30 times or more, more preferably 0.40 times or more, typically less than 1.00 times, preferably less than 0.80 times, and more preferably less than 0.70 times.

[0147] When the zeolite film is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays, the integrated intensity of 2θ = 9.6° ± 0.6° is typically 1.50 times or more, preferably 2.50 times or more, more preferably 3.00 times or more, particularly preferably 3.50 times or more, most preferably 5.00 times or more, typically 10.0 times or less, preferably 9.00 times or less, more preferably 8.00 times or less, particularly preferably 7.50 times or less.

[0148] When the zeolite membrane is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the integrated intensity at 2θ = 9.6° ± 0.6° is typically 3.00 times or more, preferably 3.50 times or more, more preferably 4.00 times or more, further preferably 5.00 times or more, particularly preferably 6.50 times or more, most preferably 10.00 times or more, typically 40.00 times or less, preferably 30.00 times or less, more preferably 25.00 times or less. When the integrated intensity ratio meets the above range, defects generated in the zeolite membrane due to thermal expansion during the manufacturing of the membrane composite, such as during firing, are reduced, thus the separation performance of the membrane composite is superior. Especially when the membrane thickness is 15 μm or less, it is preferably 3.00 times or more and 6.00 times or less.

[0149] In this embodiment, when the zeolite film is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays, the peak intensity of the peak near 2θ=17.9° can be less than 0.50 times the peak intensity of the peak near 2θ=20.8°, and the peak intensity of the peak near 2θ=9.6° can be more than 2.0 times and less than 4.0 times the peak intensity of the peak near 2θ=20.8°.

[0150] When the zeolite membrane is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the peak intensity of the peak near 2θ=17.9° is less than 0.50 times the peak intensity of the peak near 2θ=20.8°, and the peak intensity of the peak near 2θ=9.6° is more than 2.0 times but less than 4.00 times the peak intensity of the peak near 2θ=20.8°. The above ratio of the peak intensity of the peak near 2θ=17.9° to the peak intensity of the peak near 2θ=20.8° in the X-ray diffraction pattern when X-rays reaching the support are irradiated indicates that the zeolite crystals in the zeolite membrane are sufficiently oriented and grown, forming a dense zeolite membrane with high separation performance. From the viewpoint of forming a dense zeolite film with high separation performance, the ratio of the peak intensity of the peak near 2θ=17.9° to the peak intensity of the peak near 2θ=20.8° in the X-ray diffraction pattern when X-rays reach the support is irradiated is more preferably 0.49 or less. From the viewpoint of fully obtaining the effect of the above viewpoint, the lower limit of this ratio can be appropriately determined, for example, it can be 0.001 or more.

[0151] When the zeolite membrane is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the peak intensity of the peak near 2θ=17.9° is less than 0.50 times the peak intensity of the peak near 2θ=20.8°, and the peak intensity of the peak near 2θ=9.6° is more than 2.0 times but less than 4.00 times the peak intensity of the peak near 2θ=20.8°. From the viewpoint of forming a dense zeolite membrane with high separation performance, the lower limit of this ratio is preferably higher, and the upper limit of this ratio is preferably lower. For example, from the above viewpoint, the ratio of the peak intensity of the peak near 2θ=9.6° to the peak intensity of the peak near 2θ=20.8° in the X-ray diffraction pattern when X-rays reaching the support are irradiated is more preferably 2.10 or more, further preferably 2.30 or more, and even more preferably 2.50 or more. Furthermore, from the above viewpoint, this ratio is more preferably 3.90 or less, further preferably 3.80 or less, and even more preferably 3.70 or less.

[0152] In this embodiment, when the zeolite film is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays, the integrated intensity of the peak near 2θ=17.9° can be less than 0.50 times the integrated intensity of the peak near 2θ=20.8°, and the integrated intensity of the peak near 2θ=9.6° can be more than 2.0 times and less than 8.00 times the integrated intensity of the peak near 2θ=20.8°.

[0153] When the zeolite membrane is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the integrated intensity of the peak near 2θ=17.9° is less than 0.50 times the integrated intensity of the peak near 2θ=20.8°, and the integrated intensity of the peak near 2θ=9.6° is more than 2.00 times but less than 8.00 times the integrated intensity of the peak near 2θ=20.8°. In the case where the zeolite membrane is composed of CHA-type zeolite, the above-mentioned ratio of the integrated intensity of the peak near 2θ=17.9° to the integrated intensity of the peak near 2θ=20.8° in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane indicates that the zeolite crystals in the zeolite membrane are sufficiently oriented and grown, forming a dense zeolite membrane with high separation performance. From the viewpoint of forming a dense zeolite membrane with high separation performance, when the zeolite membrane is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the ratio of the integrated intensity of the peak near 2θ=17.9° to the integrated intensity of the peak near 2θ=20.8° is more preferably 0.49 or less. From the viewpoint of fully obtaining the effect of the above viewpoint, the lower limit of this ratio can be appropriately determined, for example, it can be 0.001 or more.

[0154] Furthermore, in this embodiment, when the zeolite membrane is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the integrated intensity of the peak near 2θ=17.9° is less than 0.50 times the integrated intensity of the peak near 2θ=20.8°, and the integrated intensity of the peak near 2θ=9.6° is more than 2.00 times but less than 8.00 times the integrated intensity of the peak near 2θ=20.8°. From the viewpoint of forming a dense zeolite membrane with high separation performance, the lower limit of this ratio is preferably higher, and the upper limit is preferably lower, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays. For example, when the zeolite film is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays, from the above viewpoint, the ratio of the integrated intensity of the peak near 2θ = 9.6° to the integrated intensity of the peak near 2θ = 20.8° is more preferably 2.1 or more, further preferably 2.3 or more, and even more preferably 2.5 or more. Furthermore, from the above viewpoint, this ratio is more preferably 7.50 or less, and even more preferably 7.00 or less.

[0155] In this specification, X-ray diffraction (XRD) pattern refers to the diffraction pattern obtained by irradiating the surface of the zeolite membrane of the membrane complex with X-rays using CuKα as the X-ray source and setting the scanning axis to θ / 2θ using the parallel beam method. The shape of the sample being measured is not particularly limited; however, the shape that best represents the characteristics of the membrane complex is preferably the original shape of the manufactured membrane complex or a shape cut to a suitable size limited by the measuring apparatus.

[0156] In this specification, peak intensity refers to the value obtained by subtracting the background value from the measured intensity value. Additionally, the peak intensity I near 2θ = 9.6°... 100 It refers to the intensity of the largest peak existing in the range of 9.6° ± 0.6°, mainly the intensity of the peak originating from the surface of the index (1,0,0) in the structure of zeolite. The peak intensity I near 2θ = 17.9° is... 111 This refers to the intensity of the largest peak within the range of 17.9° ± 0.6°, primarily the intensity of the peak originating from the surface with the index (1,1,1) in the zeolite structure. The peak intensity I near 2θ = 20.8° is also mentioned. 20-1 It refers to the intensity of the largest peak in the range of 20.8°±0.6°, mainly the intensity of the peaks in the structure of zeolite originating from the surface of the index (2,0,-1).

[0157] In this specification, integrated intensity refers to the value calculated by subtracting the background value from the measured intensity value. Additionally, the integrated intensity I of the peak near 2θ = 9.6°... 100 This refers to the integrated intensity of the largest peak within the range of 9.6° ± 0.6°, primarily the integrated intensity of peaks originating from the surface with the index (1,0,0) in the zeolite structure. The integrated intensity I of the peak near 2θ = 17.9° is also relevant. 111 This refers to the integrated intensity of the largest peak within the range of 17.9° ± 0.6°, primarily the integrated intensity of peaks originating from the surface with the index (1,1,1) in the zeolite structure. The integrated intensity I of the peak near 2θ = 20.8° is also relevant. 20-1 It refers to the integral intensity of the largest peak in the range of 20.8°±0.6°, mainly the intensity of the peak originating from the surface of the index (2,0,-1) in the structure of zeolite.

[0158] Orientation characteristics located further outwards than the support.

[0159] In this embodiment, when X-rays are irradiated onto the surface of the zeolite film at the minimum incident angle that penetrates the zeolite film, the integrated intensity of the peak near 2θ=9.6° in the X-ray diffraction pattern can be more than 6.0 times that of the peak near 2θ=20.8°.

[0160] "Minimum incident angle through the zeolite membrane" refers to the angle at which the peaks characteristic of the zeolite membrane can be detected when the irradiation angle of X-rays relative to the zeolite membrane is changed. It is the irradiation angle of X-rays at any of the following moments.

[0161] • When the peak characteristic of the support cannot be detected

[0162] • When the peak characteristic of the support was first detected

[0163] That is, since the measurement is performed under conditions where the limit of the support cannot be detected, the orientation of the portion of the membrane that is only further out than the support can be determined.

[0164] When X-rays are irradiated at the minimum incident angle, a high ratio of the integrated intensity of the peak near 2θ=9.6° to the integrated intensity of the peak near 2θ=20.8° in the X-ray diffraction pattern can be considered to mean, for example, that the (1,0,0) plane is oriented approximately parallel to the surface of the membrane composite when the CHA structure is set in a rhombohedral setting, thus allowing zeolite crystals to be more oriented and grow. From the viewpoint of improving the separation performance of the zeolite membrane and obtaining a dense zeolite membrane, the orientation and growth of zeolite crystals in the membrane composite is advantageous. From this viewpoint, the higher the aforementioned ratio, the better, typically 6.0 times or more, preferably 6.3 times or more, more preferably 6.5 times or more, further preferably 6.7 times or more, and particularly preferably 7.0 times or more. Among these, more preferably 10 times or more, further preferably 12 times or more, particularly preferably 15 times or more, and most preferably 20 times or more. From the viewpoint of fully obtaining the effects of the above viewpoint, the upper limit of the aforementioned ratio can be appropriately determined, for example, it can be 100 times or less.

[0165] When X-rays are irradiated at the minimum incident angle, a high ratio of the integrated intensity of the peak near 2θ=9.6° to the integrated intensity of the peak near 2θ=16.2° in the X-ray diffraction pattern can be considered to mean, for example, that the (1,0,0) plane is oriented approximately parallel to the surface of the membrane composite when the CHA structure is set in a rhombohedral setting, thus allowing zeolite crystals to be more oriented and grow. From the viewpoint of improving the separation performance of the zeolite membrane and obtaining a dense zeolite membrane, the orientation and growth of zeolite crystals in the membrane composite is advantageous. From this viewpoint, the higher the aforementioned ratio, the better; typically 6.0 times or more, preferably 6.5 times or more, more preferably 7.0 times or more, further preferably 7.5 times or more, particularly preferably 8.0 times or more, and most preferably 10.0 times or more. From the viewpoint of fully obtaining the effects of the above viewpoints, the upper limit of the aforementioned ratio can be appropriately determined, for example, it can be 100 times or less.

[0166] When X-rays are irradiated at the minimum incident angle, the integrated intensity of the peaks in the X-ray diffraction pattern can be determined by grazing incidence X-ray diffraction (GIXD). Furthermore, this integrated peak intensity can be adjusted by the conditions for zeolite film formation, for example, by the amount of seed crystals attached during hydrothermal synthesis of the zeolite film.

[0167] It should be noted that when X-rays are irradiated at the minimum incident angle, the integrated intensity of the peaks in the X-ray diffraction pattern is set as the value measured at at least one location on the film.

[0168] [film thickness]

[0169] The thickness of the zeolite membrane is typically 2 μm or more, preferably 3 μm or more, more preferably 5 μm or more, further preferably 7 μm or more, and particularly preferably 9 μm or more. When the zeolite membrane thickness is within this range, the membrane complex exhibits high strength and permeation selectivity, making it suitable for the separation and concentration of mixtures. There is no particular upper limit to the zeolite membrane thickness, but it is typically 30 μm or less, preferably 25 μm or less, more preferably 20 μm or less, and further preferably 15 μm or less. When the zeolite membrane thickness is within this range, in addition to exhibiting high separation performance by fully forming the membrane in the membrane complex, the membrane complex also exhibits high permeation flux, making it suitable for the separation and concentration of mixtures. For the separation of gas mixtures, a thickness of 5.0 μm or less is preferred, more preferably 4.0 μm or less, further preferably 3.5 μm or less, and particularly preferably 3.0 μm or less.

[0170] If the zeolite membrane is thick, the fast-reacting components in the aqueous reaction mixture will be preferentially consumed during membrane growth, thus changing the composition of the aqueous reaction mixture over time. Sometimes, the SAR (Sequential Aspect Ratio) in the thickness direction of the zeolite membrane will also change. Therefore, it is necessary to select an appropriate membrane thickness based on the structure of the target zeolite membrane.

[0171] The CF4 permeation of the porous support-zeolite membrane composite is 5.0 × 10⁻⁶. -9 mol / (m 2 When the thickness of the zeolite membrane is below 15 μm (·s·Pa), it becomes a porous support-zeolite membrane composite with particularly good permeability and separation performance.

[0172] In one aspect of the membrane composite of the present invention, the zeolite membrane is thicker than in the prior art. It is generally believed that a thicker zeolite membrane is more prone to defects. However, the zeolite membrane in one aspect of the membrane composite of the present invention, despite its relatively thick thickness, possesses specific orientation characteristics, thus preventing cracking during firing, and reducing defects as indicated by indicators such as CF4 permeation, SF6 permeation, or the product of CF4 or SF6 permeation and membrane thickness (i.e., the permeation coefficient). On the other hand, in one aspect of the membrane composite of the present invention, even if the zeolite membrane is thin, by designing it to have specific orientation characteristics, a dense membrane can be formed, reducing defects as indicated by indicators such as CF4 permeation, SF6 permeation, or the permeation coefficient of CF4 or SF6.

[0173] <Permeation characteristics of porous support-zeolite membrane composites>

[0174] The performance of a membrane composite according to one aspect of the present invention can be represented by the permeation characteristics of the membrane composite for liquids and gases.

[0175] When the measurement temperature is 50℃ and the pressure difference across the membrane is 0.3 MPa, the CF4 permeate of the membrane complex is typically 5.0 × 10⁻⁶. -9 mol / (m 2 ·s·Pa) or less, preferably 3.5×10 -9 mol / (m 2 (·s·Pa) or less, more preferably 3.0×10 -9 mol / (m 2 (·s·Pa) or less, more preferably 1.5×10 -9 mol / (m 2 ·s·Pa) or less, particularly preferably 1.0×10 - 9 mol / (m 2 The optimal value is 5.0 × 10⁻⁶ (·s·Pa). -10 mol / (m 2 Below ·s·Pa). Wherein, it can be 1.0×10 -10 mol / (m 2 (·s·Pa) or less, preferably 5.0×10 -11 mol / (m 2 (·s·Pa) or less, more preferably 3.0×10 -11 mol / (m 2 Below ·s·Pa). When the CF4 permeate of the membrane complex is within this range, the defects of permeated organic compound molecules in the membrane complex are reduced, thus the separation performance of the membrane complex is better.

[0176] The CO2 permeation capacity of the membrane complex can be 3.0 × 10⁻⁶. -4 mol / (m 2 Below 1.0 × 10⁻⁶ Pa. For the lower limit of CO₂ permeability of the membrane complex, for example, CO₂ permeability can be 1.0 × 10⁻⁶ Pa. -9 mol / (m 2 ·s·Pa) or above, 1.0×10 - 8 mol / (m 2 (·s·Pa) or above or 1.0×10 -7 mol / (m 2 (·s·Pa) or higher. When the CO2 permeation of the membrane complex is between such upper and lower limits, the membrane complex exhibits suitable permeation flux in gas separation.

[0177] The CH4 permeation capacity of the membrane complex is typically 1.0 × 10⁻⁶. -8 mol / (m 2 (·s·Pa) or less, preferably 5.0×10 -9 mol / (m 2 ·s·Pa) or less, more preferably 2.5×10 -9 mol / (m 2 (·s·Pa) or less, more preferably 2.0×10 -9 mol / (m 2 Below ·s·Pa). When the CH4 permeate of the membrane complex is within this range, the defects present in the membrane complex are reduced, and therefore the separation performance of the membrane complex is sometimes superior.

[0178] There is no specific lower limit for the N2 permeation of the membrane complex; for example, the N2 permeation can typically be 1.0 × 10⁻⁶. - 9 mol / (m 2 (·s·Pa) or higher, preferably 1.0×10 -8 mol / (m 2 (·s·Pa) or higher, more preferably 1.0×10 -7 mol / (m 2 The permeation flux of the membrane complex is above (·s·Pa). When the N2 permeation of the membrane complex is between such upper and lower limits, the membrane complex exhibits a suitable permeation flux in gas separation.

[0179] There is no particular limitation on the lower limit of He permeation of the membrane complex; for example, the He permeation can preferably be 5.0 × 10⁻⁶. - 9 mol / (m 2 (·s·Pa) or higher, more preferably 5.0×10 -8 mol / (m 2 (·s·Pa) or higher, more preferably 1.0×10 - 7 mol / (m 2 The permeate flux of the membrane complex is above 100 s·Pa. When the He permeate of the membrane complex is between such upper and lower limits, the membrane complex exhibits a suitable permeate flux in gas separation.

[0180] There is no particular limitation on the lower limit of H2 permeability of the membrane complex; for example, the preferred H2 permeability is 1.0 × 10⁻⁶. - 9 mol / (m 2 (·s·Pa) or higher, more preferably 1.0×10 -8 mol / (m 2 (·s·Pa) or higher, more preferably 1.0×10 - 7 mol / (m 2 (·s·Pa) or higher, especially preferably 1.2×10 -7 mol / (m 2 Above (·s·Pa). When the H2 permeation of the membrane complex is between such upper and lower limits, the membrane complex exhibits suitable permeation flux in gas separation.

[0181] When the measurement temperature is 50℃ and the pressure difference across the membrane is 0.3 MPa, the SF6 permeate flow rate of the membrane complex is typically 5.0 × 10⁻⁶. -9 mol / (m 2 ·s·Pa) or less, preferably 3.5×10 -9 mol / (m 2 (·s·Pa) or less, more preferably 3.0×10 -9 mol / (m 2 (·s·Pa) or less, more preferably 1.5×10 -9 mol / (m 2 ·s·Pa) or less, particularly preferably 1.0×10 - 9 mol / (m 2 The optimal value is 5.0 × 10⁻⁶ (·s·Pa). -10 mol / (m 2 Below ·s·Pa). Wherein, it can be 1.0×10 -10 mol / (m 2 (·s·Pa) or less, preferably 5.0×10 -11 mol / (m 2 (·s·Pa) or less, more preferably 3.0×10 -11 mol / (m 2 Below ·s·Pa). When the SF6 permeate of the membrane complex is within this range, the defects of permeated organic compound molecules in the membrane complex are reduced, thus the separation performance of the membrane complex is better.

[0182] In this specification, the permeation rate (permeability) of gas A in the membrane complex refers to the amount of gas A permeating the membrane complex per unit area per unit time, n. A (mol / (m 2 The value n is obtained by dividing the partial pressure p1 on the supply side of gas A by the difference (Pa) between the partial pressure p2 on the permeation side of gas A. A / (p1-p2). In this specification, unless otherwise specified, the permeation rate of gas A refers to the value measured at a temperature of 50°C and a partial pressure of 0.1 MPaG on the supply side of gas A.

[0183] [Passage Coefficient]

[0184] The CF4 or SF6 permeation of the membrane composite can be considered an indicator of its defect quantity. When studying the overall performance of the membrane composite, it is preferable to further consider the membrane thickness, which is related to permeation resistance. Therefore, in this embodiment, the permeation coefficient can be used as a measure of the defect quantity of the membrane composite, which is the product of the CF4 or SF6 permeation of the membrane composite and the thickness of the zeolite membrane. When the zeolite constituting the zeolite membrane is a CHA-type zeolite (described later), the permeation coefficient of the membrane composite, at a measurement temperature of 50°C and a pressure difference of 0.3 MPa across the membrane, is typically 4.5 × 10⁻⁴ for CF4. -8 (mol·μm) / (m 2 ·s·Pa) or less, preferably 3.5×10 -8 (mol·μm) / (m 2 (·s·Pa) or less, more preferably 3.0×10 -8 (mol·μm) / (m 2 (·s·Pa) or less, more preferably 2.0×10 -8 (mol·μm) / (m 2 ·s·Pa) or less, particularly preferably 1.0×10 -8 (mol·μm) / (m 2 Below 5.0 × 10⁻⁶ Pa, the most preferred value is 5.0 × 10⁻⁶ Pa. -9 (mol·μm) / (m 2 ·s·Pa).

[0185] When the zeolite constituting the zeolite membrane is a CHA-type zeolite (described later), the permeation coefficient of the membrane complex, at a measurement temperature of 50°C and a pressure difference of 0.3 MPa across the membrane, is typically 4.5 × 10⁻⁶ for SF6. -8 (mol·μm) / (m 2 ·s·Pa) or less, preferably 3.5×10 -8 (mol·μm) / (m 2 (·s·Pa) or less, more preferably 3.0×10 -8 (mol·μm) / (m 2 (·s·Pa) or less, more preferably 2.0×10 -8 (mol·μm) / (m 2 ·s·Pa) or less, particularly preferably 1.0×10 -8 (mol·μm) / (m 2 Below 5.0 × 10⁻⁶ Pa, the most preferred value is 5.0 × 10⁻⁶ Pa. -9 (mol·μm) / (m 2 ·s·Pa).

[0186] When the permeation coefficient of the membrane complex falls within this range, the defects present in the membrane complex are reduced, resulting in superior separation performance. It should be noted that the values ​​mentioned above refer to the values ​​of the membrane complex synthesized in the presence of an organic template, and the values ​​of the membrane complex synthesized after removing the organic template and synthesizing it in the absence of an organic template, prior to any modifications such as ion exchange treatment or silanization.

[0187] [Manufacturing method of porous support-zeolite membrane composite]

[0188] In this specification, the "method for manufacturing a porous support-zeolite membrane composite" of one aspect of the present invention is sometimes simply referred to as the "method for manufacturing a membrane composite". Hereinafter, the components and functions of the method for manufacturing a membrane composite according to one aspect of the present invention will be described. Differences from the membrane composite of one aspect of the present invention will be explained here, and matters already described in the membrane composite of one aspect of the present invention will not be repeated.

[0189] One method for manufacturing a membrane composite according to the present invention includes a loading step and a hydrothermal synthesis step.

[0190] [Loading process]

[0191] The loading process involves loading zeolite seed crystals onto a porous support. According to the loading process, the zeolite seed crystals, which function as seed crystals for zeolite crystal growth in the subsequent hydrothermal synthesis process, are loaded onto the porous support at an appropriate loading amount.

[0192] As a porous support, a porous support with the same characteristics as the above-mentioned porous supports for membrane composites can be used, such as an inorganic porous support.

[0193] The average pore diameter of the porous support is preferably 0.70 μm or more and 1.70 μm or less. By using such a porous support, a membrane composite with excellent separation performance can be manufactured. The average pore diameter of the porous support is not particularly limited, but is typically 0.70 μm or more, preferably 1.00 μm or more, more preferably 1.20 μm or more, typically 1.70 μm or less, preferably 1.50 μm or less, and more preferably 1.30 μm or less. When the average pore diameter of the porous support is within this range, defects generated in the zeolite membrane due to thermal expansion during the manufacturing of the membrane composite, such as in the hydrothermal synthesis process, are reduced, thus resulting in superior separation performance of the membrane composite.

[0194] In this specification, the average pore diameter of the porous support is the median particle size obtained by mercury porosimetry. Furthermore, the porosity of the porous support can also be determined by mercury porosimetry.

[0195] As zeolite seed crystals, zeolite particles with the same composition and pore structure as described above can be used for the zeolite membrane. For example, the zeolite seed crystals preferably have a SiO2 / Al2O3 molar ratio of 5 or more and 70 or less, and are preferably composed of CHA-type zeolite. By using such zeolite seed crystals, membrane composites with excellent separation performance can be manufactured.

[0196] The average particle size of the zeolite seed crystals is typically 0.50 μm or more, preferably 0.60 μm or more, and more preferably 0.70 μm or more. When the average particle size of the zeolite seed crystals is within this range, it further promotes the crystal growth of zeolite in the subsequent hydrothermal synthesis process, resulting in a zeolite film with a preferred film thickness. The average particle size of the zeolite seed crystals is typically 1.60 μm or less, preferably 1.40 μm or less, and more preferably 1.20 μm or less. When the average particle size of the zeolite seed crystals is within this range, the zeolite seed crystals are filled by the fine pores on the surface of the porous support, thus allowing for a further tightening of the zeolite film and the porous support in the subsequent hydrothermal synthesis process, resulting in a film composite where the zeolite film and the porous support are more closely bonded.

[0197] In this specification, the average grain size of zeolite seed crystals refers to the cumulative 50% of the grain size in the grain size distribution based on the volume scattering method determined by laser diffraction (D). 50 ).

[0198] The zeolite seed crystal loading per unit area of ​​the porous support is typically 0.10 g / m². 2 The above is preferably 0.30 g / m 2 The above, more preferably 0.50 g / m 2 The above describes the optimal loading range. When the loading is within this range, a sufficient amount of zeolite seed crystals is loaded, enabling the formation of a zeolite film in the subsequent hydrothermal synthesis process, adequately covering the surface of the porous support. The typical loading of zeolite seed crystals per unit area of ​​the porous support is 3.0 g / m². 2 The preferred value is 2.0 g / m³. 2 The preferred value is 1.5 g / m³. 2 The following is a further preferred value of 1.0 g / m 2 The following applies. When the loading is within this numerical range, the particle interfaces present in the zeolite film formed in the subsequent hydrothermal synthesis process are reduced, thus reducing defects generated at the particle interfaces. In addition, when the loading is within this numerical range, the orientation of the (1,1,1) index of the zeolite film formed in the subsequent hydrothermal synthesis process is reduced, and defects in the zeolite film caused by the thermal expansion of the porous support, i.e., film cracks, are reduced.

[0199] There are no particular limitations on the method for loading zeolite seed crystals onto a porous support. Examples include: an impregnation method in which zeolite seed crystals are dispersed in a solvent such as water and the porous support is immersed in the dispersion to allow the zeolite seed crystals to adhere to the surface of the porous support; and a coating method in which a slurry obtained by mixing zeolite seed crystals with a solvent such as water is coated onto the surface of the porous support. Among these methods, the impregnation method allows for appropriate control of the amount of zeolite seed crystals loaded, resulting in highly reproducible membrane composites, and is therefore preferred.

[0200] The solvent used to disperse the zeolite seed crystals is not particularly limited and can be water or various organic solvents, with water being preferred. An acid or alkali can be added to the dispersion to adjust the pH.

[0201] The amount of dispersed zeolite seed crystals is not particularly limited, but relative to the total mass of the dispersion, it is typically 0.01% by mass or more, preferably 0.05% by mass or more, more preferably 0.1% by mass or more, typically 3% by mass or less, preferably 2.5% by mass or less, more preferably 2.0% by mass or less, further preferably 1.5% by mass or less, and particularly preferably 1% by mass or less. When the amount of dispersed zeolite seed crystals is within such a range, the zeolite seed crystals can be easily supported on the porous support at the aforementioned loading amount.

[0202] (Hydrothermal synthesis process)

[0203] The hydrothermal synthesis process is a process of hydrothermally synthesizing a zeolite membrane on a porous support carrying zeolite seed crystals. According to the hydrothermal synthesis process, a membrane composite having a porous support and a zeolite membrane formed on the porous support can be obtained.

[0204] There are no particular limitations on the method for hydrothermal synthesis. For example, one method involves placing a porous support and a homogeneous aqueous reaction mixture with a regulated composition into a heat-resistant container such as an autoclave, sealing it, and then heating it. The aqueous reaction mixture contains a Si element source, an Al element source, and water.

[0205] There are no particular limitations on the Si and Al element sources. Examples of Si element sources include amorphous silica, colloidal silica, silica gel, sodium silicate, amorphous aluminum silicate gel, and tetraethoxysilane (TEOS) and trimethylethoxysilane. From the viewpoint of dispersibility, solubility, reactivity, and control of crystal growth during synthesis, colloidal silica is preferred as the Si element source. Examples of Al element sources include aluminum nitrate, aluminum oxide, and amorphous aluminum silicate gel. From the same viewpoint as for Si element sources, aluminum hydroxide is preferred as the Al element source.

[0206] The ratio of Si to Al source in an aqueous reaction mixture is usually expressed as the molar ratio of the oxides of each element, i.e., the SiO2 / Al2O3 molar ratio.

[0207] The ratio of water to Si source in an aqueous reaction mixture is typically expressed as the molar ratio of water to SiO2, i.e., the H2O / SiO2 molar ratio. The H2O / SiO2 molar ratio in the aqueous reaction mixture is typically 10 or more and 1000 or less, preferably 30 or more and 500 or less, more preferably 40 or more and 200 or less, and particularly preferably 50 or more and 150 or less. When the H2O / SiO2 molar ratio in the aqueous reaction mixture is within this range, the resulting zeolite membrane is dense and exhibits excellent separation performance.

[0208] The aqueous reaction mixture may further include an organic template (structure directing agent). When the aqueous reaction mixture includes an organic template, the structure selectivity of the formed zeolite film is improved, and zeolite films with the desired microporous structure can be readily obtained. The organic template can be appropriately selected according to the desired microporous structure. Examples of organic templates are described in U.S. Patent No. 4,544,538 and U.S. Patent Application Publication No. 2008 / 0075656A1.

[0209] The aqueous reaction mixture may further contain an alkaline source. Examples of alkaline sources include: hydroxide ions serving as counter anions for organic templates, alkali metal hydroxides such as NaOH and KOH, and alkaline earth metal hydroxides such as Ca(OH)₂. The type of alkaline source is not particularly limited, and is generally selected from Na, K, Li, Rb, Cs, Ca, Mg, Sr, and Ba, and any combination thereof, preferably Na or K, more preferably K. The alkaline source can be a combination of Na and K.

[0210] The heating temperature in the hydrothermal synthesis process is not particularly limited, but is typically above 100°C, preferably above 120°C, and more preferably above 150°C. Heating temperatures within this range result in zeolite films with more suitable crystallization. Furthermore, the heating temperature is typically below 200°C, preferably below 190°C, and more preferably below 180°C. Heating temperatures within this range result in zeolite films with a fine porous structure formed with higher structural selectivity.

[0211] The heating time in the hydrothermal synthesis process is not particularly limited, but is typically 1 hour or more, preferably 5 hours or more, and even more preferably 10 hours or more. Heating times within this range result in zeolite films with sufficiently grown crystals. Furthermore, the heating time is typically 10 days or less, preferably 5 days or less, more preferably 3 days or less, and even more preferably 2 days or less. Heating times within this range result in zeolite films with fine porous structures formed with higher structural selectivity.

[0212] The preferred combination of heating temperature and heating time for zeolite crystallization is a heating temperature between 170°C and 190°C, and a heating time of 16 to 20 hours. Within this range, both high permeability and high separation performance can be achieved. When the heating time is within this range, crystal growth occurs sufficiently in a direction approximately parallel to the surface of the membrane composite, forming a dense membrane and resulting in high separation performance. Within this range, the intensity of the (1,1,1) orientation is appropriate, which can improve separation performance. The (1,1,1) orientation refers to the orientation of the edges of trigonal CHA-type zeolite particles in the zeolite membrane perpendicular to the support, creating an edge-to-edge structure between the zeolite particles. It can be considered that a higher (1,1,1) orientation results in a denser, interwoven structure of particles; however, if the thermal expansion rates of the support and the zeolite membrane differ during firing, thermal expansion cannot be mitigated, leading to cracks and reduced separation performance. Therefore, it can be considered that by setting the intensity of (1,1,1) orientation to an appropriate range, the cracking of zeolite membranes can be reduced and the separation performance improved.

[0213] When the heating time is less than 16 hours, crystal growth becomes insufficient, failing to form a dense film and tending to result in poor separation performance. By extending the heating time to more than 16 hours, crystals grow sufficiently to form a dense film, making it easier to obtain high separation performance.

[0214] Furthermore, by making the H2O / SiO2 molar ratio in the aqueous reaction mixture less than 100, the reaction rate can be increased, the membrane orientation structure can be developed, and the separation performance can be improved. The H2O / SiO2 molar ratio is preferably 98 or less, more preferably 96 or less, and particularly preferably 95 or less.

[0215] The SiO2 / Al2O3 molar ratio of the seed crystal is not particularly limited, but is typically 20 or more, preferably 25 or more, more preferably 28 or more, and even more preferably 30 or more. Furthermore, the SAR of the seed crystal is typically 100 or less, preferably 80 or less, more preferably 70 or less, and even more preferably 60 or less. When the SiO2 / Al2O3 molar ratio of the seed crystal is within this range, the seed crystal partially dissolves, making it readily available as a starting point for film growth.

[0216] The (Na+K) / Al molar ratio in the aqueous reaction mixture is not particularly limited, but is typically 2.0 or higher, preferably 4.0 or higher, and more preferably 7.0 or higher. The upper limit is not particularly limited, but is 40 or lower, preferably 36 or lower, and more preferably 30 or lower. Within this range, Na and K, introduced as countercations to Al, are sufficiently present, allowing for sufficient zeolite growth and facilitating the formation of a dense film. Furthermore, by being below this upper limit, Si, as a source of elemental instability, tends to be less soluble in the aqueous reaction mixture, thus crystallization is easier to achieve, and a dense film is readily obtained.

[0217] The Na / K molar ratio of the aqueous reaction mixture is not particularly limited, but is typically 0.05 or higher, preferably 0.10 or higher, and more preferably 0.20 or higher. Additionally, it is typically 0.80 or lower, preferably 0.70 or lower, and more preferably 0.60 or lower. When these values ​​are within the above range, the growth direction of the membrane is less likely to become random, and a dense membrane is easily obtained.

[0218] When the SiO2 / Al2O3 molar ratio of the aqueous reaction mixture is 5-40, the (Na+K) / Al molar ratio of the aqueous reaction mixture is typically 4.0 or more, preferably 6.0 or more, and more preferably 7.0 or more. There is no particular upper limit, but it is 16.0 or less, preferably 15.0 or less, and more preferably 14.0 or less. Furthermore, the Na / K molar ratio of the aqueous reaction mixture is typically 0.10 or more, preferably 0.12 or more, and more preferably 0.15 or more. The upper limit is typically 0.50 or less, preferably 0.45 or less, and more preferably 0.40 or less.

[0219] The zeolite seed crystal loading per unit area of ​​the porous support is typically 0.10 g / m². 2 The above is preferably 0.30 g / m 2 The above, more preferably 0.50 g / m 2 The above describes the loading amounts. When the loading amounts are within the ranges of SiO2 / Al2O3 molar ratio, (Na+K) / Al molar ratio, and Na / K molar ratio in the aqueous reaction mixture, a sufficient amount of zeolite seed crystals is loaded, enabling the formation of a zeolite film in the subsequent hydrothermal synthesis process, adequately covering the surface of the porous support. The zeolite seed crystal loading per unit area of ​​the porous support is typically 3.0 g / m². 2 The preferred value is 2.0 g / m³. 2 The preferred value is 1.5 g / m³. 2 The following is a further preferred value of 1.0 g / m 2 the following.

[0220] When the SiO2 / Al2O3 molar ratio of the aqueous reaction mixture is 40-150, the (Na+K) / Al ratio of the aqueous reaction mixture is typically 2.0 or more, preferably 2.0 or more, and more preferably 5.0 or more. The upper limit is not particularly limited, but is 14.0 or less, preferably 13.0 or less, and more preferably 12.0 or less. Furthermore, the Na / K molar ratio of the aqueous reaction mixture is typically 0.25 or more, preferably 0.30 or more, and more preferably 0.35 or more. The upper limit is typically 0.70 or less, preferably 0.65 or less, and more preferably 0.60 or less.

[0221] The zeolite seed crystal loading per unit area of ​​the porous support is typically 0.10 g / m². 2 The above is preferably 0.40 g / m 2 The above, more preferably 0.60 g / m 2 The above describes the loading amounts. When the loading amounts are within the specified ranges for SiO2 / Al2O3 molar ratios, (Na+K) / Al molar ratios, and Na / K molar ratios, a sufficient amount of zeolite seed crystals is loaded, enabling the formation of a zeolite film in the subsequent hydrothermal synthesis process, adequately covering the surface of the porous support. The typical loading amount of zeolite seed crystals per unit area of ​​the porous support is 3.0 g / m². 2 The preferred value is 2.5 g / m³. 2 The following is more preferably 2.0 g / m 2 The following is a further preferred value of 1.5 g / m 2 the following.

[0222] In the hydrothermal synthesis process, the reaction pressure is not particularly limited. It can be the self-generated pressure generated when the porous support and aqueous reaction mixture sealed in a heat-resistant container are heated to the above-mentioned heating temperature, or it can be the pressure of adding inactive gases such as nitrogen.

[0223] (Removal process)

[0224] One embodiment of the method for manufacturing a membrane composite according to the present invention may further include a removal step after the hydrothermal synthesis step. The removal step is a step of removing impurities contained in the membrane composite. According to the removal step, impurities such as organic templates that clog the pores of zeolite and can be contained in the hydrothermally synthesized membrane composite are removed, resulting in a membrane composite with superior permeability.

[0225] There are no particular limitations on the removal method; for example, washing the membrane composite with water followed by calcination or extraction can be used. The heating temperature and time for calcination can be set appropriately.

[0226] The removal process may further include ion exchange after the removal of impurities.

[0227] [Methods for manufacturing purified organic compounds]

[0228] One aspect of the present invention is a method for producing purified organic compounds using a porous support-zeolite membrane composite having a porous support and a zeolite membrane formed on the porous support, to obtain purified organic compounds from a mixture containing organic compounds. The permeation capacity of the porous support-zeolite membrane composite for CF4 or SF6 is 5.0 × 10⁻⁶. -9 mol / (m 2 The transmittance coefficient of CF4 or SF6 is 4.5 × 10⁻⁶ (Pa·s) or less. - 8 mol·μm / (m 2 The thickness of the zeolite membrane can be 15 μm or less. According to one aspect of the present invention, a method for producing purified organic compounds can separate specific components from a fluid containing a mixture of multiple components, with organic compounds as one or more of them, with high separation efficiency, and obtain purified organic compounds as one of the components contained in the fluid. For one aspect of the present invention, the method for producing purified organic compounds shows higher separation efficiency compared to the prior art, particularly in the case of separating and concentrating aqueous organic compounds with low water content. The CF4 permeation of the above-mentioned porous support-zeolite membrane composite is 5.0 × 10⁻⁶. -9 mol / (m 2 For alternatives below ·s·Pa, the permeability coefficient of the porous support-zeolite membrane composite with SF6 or CF4 can be 4.5×10. -8 mol·μm / (m 2 The SiO2 / Al2O3 molar ratio of the zeolite membrane can be 25 or higher, and the zeolite membrane can possess the characteristics described above.

[0229] The following describes a method for purifying organic compounds according to one aspect of the present invention. Here, the differences from the membrane complex of one aspect of the present invention will be explained, and matters already described in the membrane complex of one aspect of the present invention will not be repeated.

[0230] One method of purifying organic compounds according to the present invention is as follows: a fluid containing multiple components is brought into contact with one side of a membrane complex, and a pressure difference is set on the opposite side of the membrane complex, thereby selectively permeating substances with higher permeability to the zeolite membrane to the other side of the membrane complex, while substances with lower permeability are concentrated on the contacting side.

[0231] One separation mechanism of membrane complexes is separation as a molecular sieve. One method of purifying organic compounds according to the present invention can efficiently separate components with larger effective pore diameters than those of a molecular sieve from those with smaller effective pore diameters. For example, when the zeolite membrane is composed of CHA-type zeolite, it can efficiently separate organic compounds with larger dynamic molecular diameters (compared to the effective pore diameter of 3.8 Å of a molecular sieve) from water with smaller dynamic molecular diameters.

[0232] One separation mechanism of membrane complexes utilizes the difference in hydrophilicity between water and organic compounds. The membrane complex used in one embodiment of the present invention for purifying organic compounds exhibits high hydrophilicity due to its low SiO2 / Al2O3 molar ratio, i.e., high Al2O3 content, allowing water and carbon dioxide to permeate effectively. Therefore, one embodiment of the present invention for purifying organic compounds can efficiently separate mixtures of water and organic compounds with relatively higher hydrophobicity.

[0233] Examples of organic compounds contained in fluids that are the targets of concentration include: carboxylic acids such as acetic acid, propionic acid, formic acid, lactic acid, oxalic acid, tartaric acid, and benzoic acid; organic acids such as sulfonic acids, sulfinic acids, barbituric acid, uric acid, phenol, enols, diketones, thiophenols, imides, oximes, aromatic sulfonamides, and primary and secondary nitro compounds; alcohols such as methanol, ethanol, and isopropanol; ketones such as acetone and methyl isobutyl ketone; aldehydes such as acetaldehyde; and diethyl acetate. Ethers such as alkanes and tetrahydrofurans; nitrogen-containing organic compounds (N-containing organic compounds) such as amides such as dimethylformamide and N-methylpyrrolidone; esters such as acetates, etc. From the viewpoint of obtaining purified organic compounds with higher purity by separating water with higher separation efficiency, the organic compound is preferably selected from at least one of alcohols, more preferably from at least one of alcohols with 3 or fewer carbon atoms.

[0234] When the fluid is an aqueous organic mixture, the water content of the aqueous organic mixture is not particularly limited, but is typically 30% by mass or less, preferably 25% by mass or less, and more preferably 20% by mass or less. The lower limit of the water content is not particularly limited; for example, the water content can be 1% by mass or more. In the prior art, the lower the water content of the aqueous organic mixture, i.e., the higher the content of organic compounds, the easier it is for more organic compounds to permeate through the membrane complex. However, in a method for producing purified organic compounds according to one aspect of the present invention, even when the water content of the mixture is low, as in the numerical range described above, the permeation rate of the organic compounds is reduced. Therefore, separation and concentration of the mixture can be achieved with high separation efficiency, resulting in highly purified organic compounds.

[0235] [Methods for producing purified gases]

[0236] When the fluid is a gas mixture, examples of membrane separation of gas mixtures include the separation of gaseous resources and gases emitted from thermal power plants, petrochemical industries, etc., such as the separation of carbon dioxide and nitrogen, carbon dioxide and methane, hydrogen and hydrocarbons, hydrogen and oxygen, hydrogen and carbon dioxide, nitrogen and oxygen, paraffin and olefins, helium and methane, etc. The proportion of the separated gas in the gas mixture is not particularly limited, but is typically 99% by mass or less, preferably 95% by mass or less, and more preferably 90% by mass or less. The lower limit of the proportion is not particularly limited, and for example, it can be 1% by mass or more.

[0237] [Summary of Implementation Method 1]

[0238] As can be understood from the above description, this implementation method includes the following approaches.

[0239] Method 1-1: A porous support-zeolite membrane composite, comprising a porous support and a zeolite membrane formed on the porous support, wherein the SiO2 / Al2O3 molar ratio of the zeolite membrane is 5 or more and 70 or less, and the CF4 permeation of the porous support-zeolite membrane composite is 1.0 × 10⁻⁶. -9 mol / (m 2 ·s·Pa) and below.

[0240] Method 1-2: The porous support-zeolite membrane composite according to Method 1-1, wherein the thickness of the zeolite membrane is 3 μm or more.

[0241] Methods 1-3: Porous support-zeolite membrane composites according to methods 1-1 or 1-2, wherein the CO2 permeability of the porous support-zeolite membrane composite is 1.0 × 10⁻⁶. -6 mol / (m 2 ·s·Pa) and below.

[0242] Methods 1-4: Porous support-zeolite membrane composite according to any one of methods 1-1 to 1-3, wherein the zeolite membrane is composed of CHA type zeolite.

[0243] Methods 1-5: The porous support-zeolite membrane composite according to any one of methods 1-1 to 1-4, wherein, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the peak intensity near 2θ=17.9° is more than 0.3 times and less than 1.0 times the peak intensity near 2θ=20.8°.

[0244] Methods 1-6: A method for producing purified organic compounds, comprising using a porous support-zeolite membrane composite having a porous support and a zeolite membrane formed on the porous support to obtain purified organic compounds from a mixture containing organic compounds, wherein the SiO2 / Al2O3 molar ratio of the zeolite membrane is 5 or more and 70 or less, and the CF4 permeation of the porous support-zeolite membrane composite is 1.0 × 10⁻⁶. -9 mol / (m 2 ·s·Pa) and below.

[0245] [Implementation Method 2]

[0246] Hereinafter, Embodiment 2 of the present invention will be described in detail.

[0247] [Inorganic porous support-zeolite membrane composite]

[0248] The inorganic porous support-zeolite membrane composite (hereinafter also referred to as "membrane composite") of the present invention comprises an inorganic porous support (hereinafter also referred to as "support"; it is also sometimes referred to as "porous support" in this specification) and a zeolite membrane supported on the surface of the inorganic porous support. The zeolite only needs to be fixed in a film-like form on the surface layer of the inorganic porous support, but a portion of it may also be fixed to the interior of the inorganic porous support.

[0249] The location of the zeolite film on the surface of the inorganic porous support is not limited. For example, when using a tubular inorganic porous support, the zeolite film can be located on the outer surface, the inner surface, or both surfaces of the inorganic porous support. In addition, the zeolite film can be laminated on the surface of the inorganic porous support, or it can be crystallized by filling the pores of the surface layer of the inorganic porous support.

[0250] From the viewpoint of improving the separation characteristics of membrane complexes, the zeolite membrane in the membrane complex is preferably a dense membrane, for example, the interior of a zeolite membrane formed by crystallization is substantially free of cracks or continuous micropores.

[0251] [Zeolite membrane]

[0252] The zeolite membrane in this embodiment is a membrane-like material composed of zeolite. Preferably, the zeolite membrane is formed by crystallizing zeolite on the surface layer of an inorganic porous support. The membrane composition includes zeolite, and may also include, as needed, inorganic binders such as silica or alumina, organic substances such as polymers, or silylating agents to modify the zeolite surface.

[0253] The zeolite membrane may contain amorphous components in a portion thereof, and is preferably a zeolite membrane composed substantially only of zeolite. In this embodiment, the zeolite membrane is preferably composed substantially only of CHA-type zeolite. This zeolite membrane may contain zeolite with other structures such as mordenite or MFI-type, or may contain amorphous components.

[0254] "CHA-type zeolite" refers to zeolites with a CHA structure, as defined by the International Zeolite Association (IZA). CHA-type zeolites are zeolites with a crystal structure identical to that of naturally occurring chalcogenide. CHA-type zeolites possess a three-dimensional porous structure formed by oxygen 8-membered rings with a diameter of 3.8 × 3.8 Å, which can be characterized by X-ray diffraction data.

[0255] In this embodiment, the framework density of the CHA-type zeolite is 14.5 T / 1000 Å. Framework density refers to the density of the zeolite per 1000 Å. 3 The number of elements other than oxygen that make up the framework. This value is determined by the structure of the zeolite. It should be noted that the relationship between framework density and zeolite structure is shown in ATLAS OF ZEOLITE FRAMEWORK TYPES Fifth Revised Edition 2001 ELSEVIER.

[0256] In this embodiment, the SiO2 / Al2O3 molar ratio of the CHA-type zeolite is not particularly limited, but is generally 10 or more, preferably 15 or more, more preferably 18 or more, even more preferably 20 or more, and particularly preferably 25 or more. As an upper limit for the above molar ratio, it is generally 70 or less, preferably 60 or less, and more preferably 50 or less. This is the same as the SiO2 / Al2O3 molar ratio of the zeolite film described later.

[0257] <Orientation Characteristics>

[0258] The ratio of the intensity A of the (1,0,0) orientation to the intensity B of the (2,0,-1) orientation in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film of this embodiment with X-rays is more than 0.7 times.

[0259] In this embodiment, the "X-ray diffraction pattern" is obtained by irradiating the surface of the zeolite membrane of the membrane composite with CuKα as the radiation source and setting the scanning axis to θ / 2θ. The shape of the sample being measured is only required to allow X-ray irradiation of the surface of the zeolite membrane of the membrane composite. From the viewpoint of well representing the characteristics of the membrane composite, the sample is preferably the manufactured membrane composite itself, or, if limited by the apparatus, preferably a cut-off piece of the membrane composite of an appropriate size. When the surface of the membrane composite is curved, the X-ray diffraction pattern can be measured using an automatically variable slit with a fixed irradiation width. The X-ray diffraction pattern using an automatically variable slit is a pattern that has undergone variable-to-fixed slit correction.

[0260] The intensity A of the (1,0,0) orientation (sometimes referred to as "peak intensity I" in this specification) 100 The peak at 2θ = 9.6° in the X-ray diffraction pattern is the largest peak among those not originating from the substrate (inorganic porous support) that exists within the range of 9.6° ± 0.6°. The peak intensity is obtained by processing the measured intensity. Additionally, the intensity A of the (2,0,-1) orientation (sometimes referred to as "peak intensity I" in this specification) is also considered. 20-1 The peak near 2θ=20.8° in the X-ray diffraction pattern is the largest peak in the range of 20.8°±0.6° that does not originate from the substrate (inorganic porous support).

[0261] It can be considered that a ratio A / B of 0.7 or more for the intensity A of the (1,0,0) orientation to the intensity B of the (2,0,-1) orientation means that when zeolite crystals are grown on an inorganic porous support, crystal growth is carried out appropriately along an orientation approximately parallel to the surface of the membrane composite, resulting in a dense membrane with high separation performance. From this viewpoint, an intensity ratio A / B of 0.7 or more is preferred, more preferably 0.9 or more, and even more preferably 1.0 or more. Furthermore, from the viewpoint of forming a dense membrane with both high permeability and high separation performance, an intensity ratio A / B of 100 or less is preferred.

[0262] Furthermore, from the viewpoint of improving the separation performance of the zeolite membrane and forming a dense zeolite membrane, the ratio G / B of the intensity G of the (1,1,1) orientation to the intensity B of the (2,0,-1) orientation is preferably 0.3 or more, more preferably 0.35 or more, and even more preferably 0.4 or more. The intensity G of the (1,1,1) orientation (sometimes referred to as "peak intensity I" in this specification) 111 The term "" refers to the peak near 2θ = 17.9° in the X-ray diffraction pattern, which is the largest peak in the range of 17.9° ± 0.6° that does not originate from the substrate (inorganic porous support). From the above point of view, the intensity ratio G / B is preferably 1.0 or less, more preferably 0.9 or less, and even more preferably 0.8 or less.

[0263] Separation performance can be improved by keeping the intensity of the (1,1,1) orientation within the aforementioned range. The (1,1,1) orientation refers to the orientation of the edges (corners) of trigonal CHA-type zeolite particles in the zeolite film perpendicular to the support, resulting in an edge-to-edge structure between the zeolite particles. It can be considered that a higher (1,1,1) orientation leads to a denser, more interwoven structure of particles. However, during firing, if the thermal expansion rates of the support and the zeolite film differ, thermal expansion cannot be mitigated, causing cracks in the zeolite film and reducing separation performance. Therefore, it can be considered that by setting the intensity of the (1,1,1) orientation within the aforementioned range, cracks in the zeolite film can be reduced, thus improving separation performance.

[0264] Regarding other orientation characteristics, they are preferably the same as those described in Embodiment 1. This will not be repeated here.

[0265] The peak near 2θ = 9.6° (9.6° ± 0.6°) in the X-ray diffraction pattern is, according to the *Collection of Simulated XRD Powder Patterns for ZEOLITE Fourth Revised Edition 2001*, originating from the plane with indices (1,0,0) in the CHA structure when the space group is set to (No. 166) in the rhombohedral setting. Additionally, the peak near 2θ = 20.8° (20.8° ± 0.6°) in the X-ray diffraction pattern is, according to the *Collection of Simulated XRD Powder Patterns for ZEOLITE Fourth Revised Edition 2001*, originating from the plane with indices (2,0,-1) in the CHA structure when the space group is set to (No. 166) in the rhombohedral setting.

[0266] <sar>

[0267] In this embodiment, the SiO2 / Al2O3 molar ratio (hereinafter also referred to as "surface SAR") of the zeolite membrane surface portion is 25 or higher. The zeolite membrane of this embodiment exhibiting such SAR demonstrates high acid resistance. From the viewpoint of improving acid resistance, the SAR of the zeolite membrane surface portion is typically 25 or higher, preferably 26 or higher, more preferably 27 or higher, and even more preferably 28 or higher. On the other hand, if the SAR of the zeolite membrane is too high, there is a tendency for the transmittance to decrease. From this viewpoint, the SAR of the zeolite membrane surface portion is typically 70 or lower, preferably 60 or lower, and more preferably 50 or lower.

[0268] "The surface portion of a zeolite membrane" refers to a portion of the surface side of the zeolite membrane in the thickness direction. (Usage) Figure 1 The thickness direction of the zeolite film in this embodiment will be explained.

[0269] Figure 1 This is a diagram illustrating a portion of the zeolite membrane in the thickness direction of the present invention. The membrane composite 10 is composed of a zeolite membrane 11 and an inorganic porous support 12. The zeolite membrane 11 is formed on the surface of the inorganic porous support 12. Figure 1 The horizontal direction of the image is set in such a way that the interface between the support and the membrane is horizontal.

[0270] Figure 1 In the image, point A is the most concave part of the surface in the cross-sectional image of the zeolite membrane. Point B is the intersection of the inorganic porous support with the straight line passing through point A and along the membrane thickness direction. Point C is the midpoint of line segment AB. Figure 1 In the image, L1 is a line passing through point A and perpendicular to the film thickness direction, and L2 is a line perpendicular to the film thickness direction and is the tangent to the most concave part of the inorganic porous support in the cross-sectional image of the zeolite film. Point D represents a position 1 μm deep from point A (line L1) along the film thickness direction, and point E represents a position 1 μm shallower than line L2 along the film thickness direction.

[0271] The surface portion 11A of the zeolite membrane is a region extending perpendicular to the thickness direction and including point D in the cross-section of the zeolite membrane. It has a depth of 1 μm and a width of 24 μm from point D on the inorganic porous support side. The central portion 11B of the zeolite membrane is a region extending perpendicular to the thickness direction and including point C in the cross-section of the zeolite membrane. It has a depth of ±0.5 μm and a width of 24 μm from point C. It should be noted that 11C is the bottom of the zeolite membrane, a region extending perpendicular to the thickness direction and including point E in the cross-section of the zeolite membrane. It has a depth of 1 μm and a width of 24 μm from point E on the surface side.

[0272] The higher the uniformity of the SAR (Separation Characteristics) of zeolite membranes along the film thickness direction, the better the separation performance. From the viewpoint of improving separation performance, the ratio of the SiO2 / Al2O3 molar ratio C at the surface of the zeolite membrane to the SiO2 / Al2O3 molar ratio D at the center along the film thickness direction (SAR ratio C / D) is preferably less than 1.5, more preferably 1.4 or less, and even more preferably 1.3 or less. The lower the SAR ratio C / D is within the achievable range, the better; for example, from the viewpoint of being achievable by the manufacturing method described later, it can be 1.0 or more.

[0273] Alternatively, from the viewpoint of improving separation characteristics, the difference (CD) between the SiO2 / Al2O3 molar ratio C at the surface portion of the zeolite membrane and the SiO2 / Al2O3 molar ratio D at the central portion in the thickness direction of the membrane is preferably less than 10, more preferably 8 or less, and even more preferably 6 or less. The aforementioned difference CD of SAR is as low as possible within the achievable range, for example, from the viewpoint of being achievable by the manufacturing method described later, it can be 0.1 or more.

[0274] SAR can be obtained using scanning electron microscopy-energy dispersive X-ray spectroscopy (SEM-EDX). To obtain information on films as small as a few micrometers, the accelerating voltage of the X-rays is typically set to 6 kV for measurement.

[0275] In the aforementioned bottom 11C, when the cross-section of the zeolite membrane is exposed, if the cross-section is not exposed approximately perpendicular to the support, or depending on the membrane thickness, silica and alumina in the inorganic porous support are sometimes detected. The aforementioned SAR ratio C / D and SAR difference CD are derived based on the detection results of the surface portion 11A and the central portion 11B. In the surface portion 11A and the central portion 11B, silica and alumina in the inorganic porous support are generally not detectable. Thus, the SAR ratio C / D and SAR difference CD are derived based on the SAR of the portion substantially unaffected by the inorganic porous support, representing the thickness-direction characteristics of the zeolite membrane itself.

[0276] In this embodiment, the SiO2 / Al2O3 molar ratio (hereinafter also referred to as "surface SAR") measured from the surface of the zeolite membrane is 20 or higher. The zeolite membrane of this embodiment exhibiting such SAR demonstrates high acid resistance. From the viewpoint of improving acid resistance, the SAR of the surface portion of the zeolite membrane is typically 22 or higher, preferably 23 or higher, more preferably 24 or higher, and even more preferably 25 or higher. On the other hand, if the SAR of the zeolite membrane is too high, there is a tendency for the transmittance to decrease. From this viewpoint, the SAR of the surface portion of the zeolite membrane is typically 70 or lower, preferably 60 or lower, and more preferably 50 or lower.

[0277] "Measurement from the surface of zeolite film" refers to the determination of the SiO2 / Al2O3 molar ratio on the outer surface of the zeolite film. Specifically, the SiO2 / Al2O3 molar ratio at more than 9 points in a region of (2±0.5μm)×(2±0.5μm) is determined using three different 5000x surface images, and the average value is taken as the surface SAR.

[0278] [film thickness]

[0279] The thickness of the zeolite membrane in this embodiment can be appropriately determined within a range that yields the desired characteristics. From this perspective, the thickness of the zeolite membrane can be 2 μm or more, or 3 μm or more. Furthermore, considering the above, the thickness of the zeolite membrane can be 100 μm or less, preferably 60 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, particularly preferably 20 μm or less, and most preferably 15 μm or less. When the zeolite membrane of this embodiment is used for the separation of gas mixtures, a thickness of 5.0 μm or less is preferred, more preferably 4.0 μm or less, even more preferably 3.5 μm or less, and particularly preferably 3.0 μm or less.

[0280] From the viewpoint of accurately judging the uniformity of SAR of the zeolite membrane, the minimum thickness of the zeolite membrane is preferably 2 μm or more, and more preferably 2.5 μm or more. When using the zeolite membrane of this embodiment in the pervaporation method or the vapor permeation method, the minimum thickness of the zeolite membrane can be 5 μm or more. "Minimum thickness of the zeolite membrane" refers to the minimum value in the cross-sectional image of the zeolite membrane.

[0281] <particle size>

[0282] When the zeolite particle size constituting the zeolite film is too small, there is a tendency for the grain boundaries to become larger, leading to a decrease in transmittance selectivity. From this perspective, the zeolite particle size can be 30 nm or larger, preferably 50 nm or larger, and more preferably 100 nm or larger. The upper limit of this particle size is less than or equal to the film thickness of the zeolite film. From the above perspective, it is preferable that the zeolite grain boundaries in the zeolite film are small; therefore, it is preferable that the zeolite particle size is the same as the film thickness. Zeolite films obtained through hydrothermal synthesis sometimes have the same zeolite particle size as the film thickness, which is therefore preferred. It should be noted that the "zeolite particle size" can be determined from a TEM image of the cross-section of the zeolite film.

[0283] [Inorganic Porous Support (Porous Support)]

[0284] In this embodiment, the inorganic porous support may suitably be the inorganic porous support described in Patent Document 1 or Patent Document 2.

[0285] The inorganic porous support is preferably porous and possesses the chemical stability to crystallize zeolite into a film on its surface. Examples of inorganic porous supports include sintered ceramic bodies, sintered metals, glass-formed bodies, and carbon-formed bodies. Examples of ceramics used in sintered ceramic bodies include silica, α-alumina, γ-alumina, mullite, zirconium oxide, titanium dioxide, yttrium oxide, silicon nitride, and silicon carbide. Examples of sintered metals include iron, bronze, and stainless steel.

[0286] From the viewpoint of improving the adhesion to the zeolite membrane during its synthesis, a ceramic sintered body is preferred. Among these, a sintered body made of one or more ceramics selected from alumina, silica, and mullite is preferred, as it tends to further improve separation performance when the zeolite membrane is a CHA-type zeolite.

[0287] The shape of the inorganic porous support can be appropriately determined within the scope of its applicability to membrane composites. Examples of shapes for inorganic porous supports include flat plates, tubular shapes, cylindrical shapes, honeycomb structures with multiple cylindrical and prismatic pores, and monoliths.

[0288] When the average thickness (wall thickness) of the inorganic porous support is too thin, the strength of the membrane composite decreases, which tends to cause practical problems. When the wall thickness of the inorganic porous support is too thick, the components that permeate through the inorganic porous support are difficult to diffuse, which tends to reduce the permeation flux of the permeated components. From the viewpoint of achieving appropriate diffusion of permeated components and sufficient strength of the inorganic porous support, the wall thickness of the inorganic porous support is preferably 0.1 mm or more, more preferably 0.3 mm or more, even more preferably 0.5 mm or more, and preferably 7 mm or less, more preferably 5 mm or less, and even more preferably 3 mm or less.

[0289] When a zeolite film is formed on the surface of an inorganic porous support, the zeolite crystallizes in the surface layer of the inorganic porous support to form a film. From the viewpoint of affecting the seed crystal's support state on the substrate or its permeability, the average pore diameter of this surface layer is preferably 0.02 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more. Furthermore, from the viewpoint of affecting the seed crystal's support state on the substrate or its permeability, the average pore diameter is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less.

[0290] Furthermore, from the viewpoint of ensuring a uniform and position-independent support state for the seed crystal, a smooth surface of the inorganic porous support is preferred. A smooth surface can be achieved as needed by grinding with a file or similar tool.

[0291] It should be noted that the surface layer of the inorganic porous support refers to the surface and the portion near it in the thickness direction of the inorganic porous support used to crystallize zeolites such as CHA-type zeolites. The shape of this surface layer in top view and its position (main surface, etc.) on the surface of the inorganic porous support are not limited. This surface layer can be located on multiple surfaces of the inorganic porous support. For example, when the inorganic porous support is cylindrical, the surface layer can be located on the outer circumferential surface, the inner circumferential surface, or both circumferential surfaces.

[0292] There is no limit to the diameter of the pores in the portion of the inorganic porous support other than the surface layer.

[0293] The porosity of the portion of an inorganic porous support outside its surface layer affects the permeation flux during gas or liquid separation. If the porosity is too low, it tends to hinder the diffusion of the permeate; if it is too high, it tends to reduce the strength of the inorganic porous support. From the viewpoint of achieving appropriate diffusion of the permeate and sufficient strength of the inorganic porous support, the porosity of the portion of the inorganic porous support outside its surface layer is preferably 20% or more and 60% or less.

[0294] <Permeation Characteristics of Membrane Complexes>

[0295] In this embodiment, the CF4 permeation rate in the membrane composite is preferably 5.0 × 10⁻⁶. -9 mol / (m 2 Below 10⁻⁶ Pa. CF₄ permeate refers to the presence of defects in a zeolite membrane used to separate water from aqueous solutions of organic compounds such as alcohols. From the viewpoint of fewer defects and better separation performance, the CF₄ permeate is preferably 3.5 × 10⁻⁶ Pa at a measurement temperature of 50°C and a pressure difference of 0.3 MPa across the membrane. -9 mol / (m 2 (·s·Pa) or less, more preferably 3.0×10 -9 mol / (m 2 (·s·Pa) or less, more preferably 1.5×10 -9 mol / (m 2 ·s·Pa) or less, particularly preferably 1.0×10 -9 mol / (m 2 The optimal value is 5.0 × 10⁻⁶ (·s·Pa). -10 mol / (m 2 Below ·s·Pa). Wherein, it can be 1.0×10 -10 mol / (m 2 (·s·Pa) or less, preferably 5.0×10 -11 mol / (m 2 (·s·Pa) or less, more preferably 3.0×10 -11 mol / (m 2 ·s·Pa) and below.

[0296] The CO2 permeation rate in the membrane composite of this embodiment is preferably 1×10⁻⁶. -6 mol / (m 2 CO2 permeation typically tends to be higher in zeolite membranes with high SAR (Specific Absorption Rate). This is because the membrane thickness of a zeolite membrane with high SAR is easily reduced, thus allowing CO2 to permeate more easily. In this embodiment, the SAR of the zeolite membrane tends to be high not only at the surface but also uniformly so in the membrane thickness direction. Therefore, from the viewpoint that zeolite membranes with high SAR have fewer defects and superior separation characteristics, the membrane composite of this embodiment preferably has the aforementioned CO2 permeation.

[0297] It should be noted that the gas permeation rate in the membrane complex of this embodiment is determined by the amount of gas permeating the membrane complex per unit area and per time, n(mol / (m²)). 2 The value n / (p1-p2) is obtained by dividing the partial pressure p1 on the gas supply side and the partial pressure p2 on the gas permeation side by the gas permeation side (Pa). The gas permeation rate described above can be measured at a temperature of 50°C and a partial pressure of 0.3 MPaG on the gas supply side. Unless otherwise specified, the partial pressure on the gas supply side is set to 0.1 MPaG.

[0298] [Manufacturing method of membrane complex]

[0299] The method for manufacturing the membrane composite of this embodiment can be carried out using known methods capable of manufacturing the membrane composite within a range that can appropriately exhibit the above-described characteristics. Examples of such known methods include: a method for crystallizing zeolite into a membrane on an inorganic porous support; a method for fixing zeolite to an inorganic porous support using an inorganic binder or an organic binder; a method for fixing a polymer in which zeolite is dispersed; and a method for impregnating a slurry of zeolite into an inorganic porous support and, as appropriate, for fixing the zeolite to the inorganic porous support by suction.

[0300] A preferred method for manufacturing the membrane composite of this embodiment is to crystallize zeolite into a film on the surface layer of an inorganic porous support. More specifically, a preferred method for manufacturing the membrane composite of this embodiment is to crystallize CHA-type zeolite into a film on the surface layer of an inorganic porous support by hydrothermal synthesis. In such a manufacturing method, the manufacturing method described in Patent Document 1 can be applied.

[0301] When CHA-type zeolite is crystallized in a film-like form on the surface layer of an inorganic porous support, seed crystals may not be necessary. However, from the viewpoint of promoting the crystallization of CHA-type zeolite, it is preferable to add seed crystals to the reaction system. Examples of methods for adding seed crystals include adding seed crystals to the reaction mixture used to synthesize the CHA-type zeolite film, and attaching seed crystals to the surface of the inorganic porous support. From the viewpoint of easily generating a dense zeolite film with good separation performance, the method of adding seed crystals is preferably the method of pre-attaching seed crystals to the surface of the inorganic porous support.

[0302] The seed crystal can be any zeolite that promotes crystallization. From the viewpoint of efficient crystallization, CHA-type zeolite is preferred as the seed crystal. The smaller the particle size of the CHA-type zeolite used as the seed crystal, the better, and it can be used by pulverization as needed. This particle size, in terms of average particle size, is generally 0.5 nm or more, preferably 1 nm or more, more preferably 2 nm or more, generally 5 μm or less, preferably 3 μm or less, and even more preferably 2 μm or less. The average particle size of the seed crystal is the particle size (D) that accounts for 50% of the cumulative particle size in the particle size distribution on a volume basis determined by laser diffraction scattering. 50 ).

[0303] Examples of methods for attaching seed crystals to the surface of an inorganic porous support include: an impregnation method in which seed crystals are dispersed in a solvent such as water, and the inorganic porous support is immersed in the dispersion to attach the seed crystals to its surface; and a method of coating a slurry made by mixing seed crystals with a solvent such as water onto the surface of the inorganic porous support. From the viewpoint of controlling the amount of seed crystals attached and manufacturing the membrane composite with good reproducibility, the method for attaching seed crystals is preferably the impregnation method.

[0304] Water is the preferred solvent for dispersing the seed crystals. If the amount of dispersed seed crystals is too small, the amount of seed crystals adhering to the inorganic porous support will be insufficient. Therefore, during hydrothermal synthesis, areas where CHA-type zeolite does not form may sometimes appear on the surface of the inorganic porous support, potentially resulting in defective zeolite films. Conversely, if the amount of dispersed seed crystals is too large, the amount of seed crystals adhering to the surface of the inorganic porous support remains relatively constant, leading to increased seed crystal waste and a cost disadvantage. From the viewpoint of preventing defects in the zeolite film and reducing costs, the amount of seed crystals in the dispersion is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.5% by mass or more. Furthermore, from the above viewpoints, the amount of seed crystals in the dispersion is preferably 20% by mass or less, more preferably 10% by mass or less, even more preferably 5% by mass or less, and even more preferably 3% by mass or less.

[0305] In the manufacture of membrane composites, it is preferable to attach seed crystals to the surface of an inorganic porous support by impregnation or slurry coating, and then synthesize zeolite membranes after drying.

[0306] When the amount of seed crystals attached to the surface of an inorganic porous support is too low, zeolite crystallization is difficult to form, sometimes resulting in insufficient or uneven zeolite film growth. Therefore, it is sometimes difficult to form a dense zeolite film. Regarding the amount of seed crystals attached, sometimes the surface unevenness of the inorganic porous support is increased due to the seed crystals, or sometimes the spontaneous growth of crystal nuclei is facilitated by seed crystals detached from the surface of the inorganic porous support, hindering film growth on the inorganic porous support. Therefore, it is sometimes difficult to form a dense zeolite film. From the viewpoint of easily forming a dense zeolite film, the amount of seed crystals attached should be such that per 1m... 2 The mass of the inorganic porous support is preferably 0.01 g or more, more preferably 0.05 g or more, and even more preferably 0.1 g or more. Furthermore, based on the above viewpoint, the amount of seed crystals attached is expressed as per 1m³. 2 The mass of the inorganic porous support is preferably 100g or less, more preferably 50g or less, even more preferably 10g or less, and even more preferably 8g or less.

[0307] When zeolite is crystallized via hydrothermal synthesis, any method can be used to immobilize the inorganic porous support, including both longitudinal and transverse placement. In the above cases, crystallization can be achieved by static settling or by stirring the reaction mixture.

[0308] When the temperature for crystallizing zeolite is too low, CHA-type zeolite may not crystallize; when it is too high, zeolite of a different type from CHA-type may be formed. From the viewpoint of crystallizing CHA-type zeolite, the crystallization temperature is preferably 100°C or higher, more preferably 120°C or higher, and even more preferably 150°C or higher. Furthermore, considering the above viewpoints, the crystallization temperature is preferably 200°C or lower, more preferably 190°C or lower, and even more preferably 180°C or lower.

[0309] If the heating time for crystallizing zeolite is too short, CHA-type zeolite may not crystallize; if it is too long, zeolite of a different type from CHA-type may form. From the viewpoint of crystallizing CHA-type zeolite, the heating time is preferably 1 hour or more, more preferably 5 hours or more, and even more preferably 10 hours or more. Furthermore, from the above viewpoint, the heating time is preferably 10 days or less, more preferably 5 days or less, even more preferably 3 days or less, particularly preferably 2 days or less, and most preferably less than 24 hours.

[0310] The preferred combination of heating temperature and heating time for zeolite crystallization is 170-190°C for 16-20 hours. Within this range, both high permeability and high separation performance can be achieved. When the heating time is within this range, sufficient crystal growth along an orientation approximately parallel to the membrane composite can be achieved, forming a dense membrane and obtaining high separation performance. Within this range, the intensity of the (1,1,1) orientation is appropriate, which can improve separation performance. The (1,1,1) orientation refers to the orientation of the edges of trigonal CHA-type zeolite particles in the zeolite membrane perpendicular to the support, resulting in an edge-to-edge structure between the zeolite particles. It can be considered that a higher (1,1,1) orientation leads to a denser, interwoven structure of particles; however, if the thermal expansion rates of the support and the zeolite membrane differ during firing, thermal expansion cannot be mitigated, leading to cracks and sometimes a decrease in separation performance. Therefore, it can be considered that by setting the intensity of the (1,1,1) orientation within an appropriate range, cracks in the zeolite membrane can be reduced, and separation performance can be improved. Other matters are the same as those described in Embodiment 1.

[0311] The pressure during crystallization is sufficient to be the self-generated pressure generated when the reaction mixture placed in a sealed container is heated to the temperature range mentioned above, but inactive gases such as nitrogen can be added to adjust the pressure.

[0312] The membrane composite obtained by hydrothermal synthesis preferably has its organic template removed from the zeolite membrane after water washing. Methods for removing the organic template include calcination or extraction, with calcination being the preferred method.

[0313] If the firing temperature during organic template removal is too low, the proportion of residual organic template increases, and the number of pores in the zeolite membrane decreases, potentially reducing the permeation flux during separation and concentration. If the firing temperature is too high, the difference in thermal expansion between the inorganic porous support and the zeolite membrane increases. Therefore, there is a possibility that the zeolite membrane is prone to cracking, and sometimes the zeolite membrane loses its density, resulting in reduced separation performance. From the viewpoint of suppressing the decrease in permeation flux and separation performance during separation and concentration, the firing temperature is preferably 350°C or higher, more preferably 400°C or higher, even more preferably 430°C or higher, and even more preferably 480°C or higher. Furthermore, from the above viewpoint, the firing temperature is preferably 900°C or lower, more preferably 850°C or lower, even more preferably 800°C or lower, and even more preferably 750°C or lower.

[0314] The firing time for removing the organic template can be appropriately determined within a range that allows for sufficient removal of the organic template, for example, preferably 1 hour or more, more preferably 5 hours or more. There is no upper limit to the firing time, and it can be up to 24 hours. Firing can be carried out in an air atmosphere or in an oxygen-containing gas atmosphere.

[0315] From the viewpoint of suppressing cracking of the zeolite film due to the difference in thermal expansion between the inorganic porous support and the zeolite film, the heating rate during firing is preferably slower. From this viewpoint, this heating rate is preferably 5°C / min or less, more preferably 2°C / min or less, even more preferably 1°C / min or less, and even more preferably 0.5°C / min or less. From an operability viewpoint, this heating rate can be 0.1°C / min or more.

[0316] Furthermore, from the viewpoint of avoiding cracks in the zeolite film, the cooling rate after firing is preferably slower than the heating rate. From this perspective, the cooling rate is preferably 5°C / min or less, more preferably 2°C / min or less, even more preferably 1°C / min or less, and even more preferably 0.5°C / min or less. From an operability perspective, the cooling rate can be 0.1°C / min or more.

[0317] Ion exchange treatment can be performed on the manufactured membrane composite as needed. When synthesizing zeolite membranes using an organic template, ion exchange is preferably performed after processes such as calcination to remove the organic template. Examples of ions that can be exchanged include: protons, Na+, and other ions. + K + and Li + Alkali metal ions, Ca 2+ Mg 2+ 、Sr 2+ And Ba 2+ Alkaline earth metal ions, and transition metal ions such as Fe, Cu, and Zn. Among them, proton or alkali metal ions are preferred.

[0318] Ion exchange can be carried out, for example, by treating the calcined membrane composite (in cases where an organic template is used) with ammonium salts such as NH4NO3 and NaNO3 or an aqueous solution containing the ions to be exchanged, or with acids such as hydrochloric acid as appropriate, usually at a temperature of room temperature to 100°C, washing with water, and calcining at 200 to 500°C as needed.

[0319] [Method for manufacturing purified components]

[0320] The membrane complex of this embodiment can be used to manufacture purified components. In the manufacture of such purified components, a mixture of a first component that permeates through the zeolite membrane of the membrane complex of this embodiment and a second component that does not permeate through the zeolite membrane is brought into contact with the membrane complex. In this method, a first purified component that permeates through the zeolite membrane, a second purified component that does not permeate through the zeolite membrane, or both can be obtained. In this embodiment, the component after the second component has been removed from the first component by the membrane complex is called the first purified component, and the component after the first component has been removed from the second component by the membrane complex is called the second purified component.

[0321] The method for producing the purified component in this embodiment can be applied to either liquids or gases. That is, both the first and second components can be liquids, or both the first and second components can be gases.

[0322] Furthermore, both the first and second components can be inorganic or organic substances. Additionally, both the first and second components can be individual components or a mixture of two or more components. For example, one of the first and second components can be water, and the other can be a water-soluble organic compound.

[0323] Furthermore, the membrane complex of this embodiment exhibits excellent acid resistance. Therefore, in the method for producing the purified component, one of the first and second components can be water, and the other can contain an acid. Such a method for producing the purified component can be implemented, for example, in the same manner as the separation or concentration using a membrane complex described in Patent Document 1.

[0324] For example, the method for manufacturing the purified component in this embodiment is as follows: a mixture of gas or liquid containing organic matter (a mixture of the first component and the second component) is brought into contact with one side of an inorganic porous support or a zeolite membrane via a membrane composite, and the pressure on the other side is set to a lower pressure than that on the first side. A permeable substance (one of the highly permeable substance in the mixture, the first component, and the second component) is selectively allowed to permeate through the CHA-type zeolite membrane from the mixture. Thus, the highly permeable substance can be separated from the mixture.

[0325] Furthermore, as a result, by increasing the concentration of specific organic compounds (substances with low permeability in the mixture) in the mixture containing organic matter, specific organic compounds can be separated, recovered, or concentrated. More specifically, in the case of a mixture of water and organic matter, water typically has high permeability to the zeolite membrane. Therefore, water permeates through the zeolite membrane, resulting in the separation of water and organic matter from the mixture, with the organic matter being concentrated in the original mixture. This separation / concentration method, known as permeation vaporization or vapor permeation, is one of the methods for producing the purified components in this embodiment.

[0326] In the method for manufacturing purified components, the membrane complex can be of any shape, such as tubular, hollow fiber, monolithic, or honeycomb. Furthermore, the size of the membrane complex is not limited; from a practical point of view, in the case of a tubular shape, the length is preferably 2 cm or more and 200 cm or less, the inner diameter is preferably 0.5 cm or more and 2 cm or less, and the thickness is preferably 0.5 mm or more and 4 mm or less.

[0327] One of the separation functions of the membrane complex is as a molecular sieve. For the method of manufacturing the purified component in this embodiment, the effective pore diameter of the CHA-type zeolite is 3.8 Å, which is suitable for separating gas or liquid molecules of a size greater than or equal to that of smaller gas or liquid molecules. It should be noted that the size of the molecules to be separated (the first or second component that does not permeate the zeolite membrane) is typically around 100 Å or less.

[0328] Another separation function of membrane complexes is the separation function utilizing differences in hydrophilicity. Although it depends on the type of zeolite, hydrophilicity is usually further enhanced by containing a certain amount of Al in the zeolite framework within the zeolite membrane. By controlling the crystallization conditions of CHA-type zeolite membranes, the SAR in the crystals can be controlled. If such hydrophilic zeolite membranes are used, water molecules can be selectively permeated through the membrane from a mixture of organic matter and water, allowing for the separation and concentration of organic matter from the mixture.

[0329] Examples of this mixture include aqueous solutions of organic matter and water (organic matter / water), and more specifically include: organic acids / water, alcohols / water, ketones such as acetone and methyl isobutyl ketone / water, aldehydes / water, and diethyl esters. Ethers such as alkanes and tetrahydrofurans / water, nitrogen-containing organic compounds such as dimethylformamide and N-methylpyrrolidones / water, and esters such as acetates / water.

[0330] The water content in the mixture of organic matter and water is not limited. Even in mixtures with high water content, such as 20% by mass or more, where the structure of type A zeolite would be destroyed, high selectivity and permeation flux can be achieved in the method for manufacturing the purified component of this embodiment using the membrane complex of this embodiment.

[0331] Furthermore, the membrane composite of this embodiment has high acid resistance, so the method for manufacturing the purified component of this embodiment can be used even in systems other than the above-mentioned organic acid / water, for example, even if organic or inorganic acids are present.

[0332] Thus, for the membrane complex of this embodiment, in the method for manufacturing the purified component of this embodiment, high selectivity and permeation flux can be achieved even when separating water from a mixture with organic matter of high water content or under acidic conditions. Therefore, specific components in a mixture that are normally separated by distillation can be separated by the method for manufacturing the purified component of this embodiment, resulting in a reduction of the energy required for separation compared to distillation.

[0333] Furthermore, in the method for manufacturing the purified component in this embodiment, water can be separated from mixtures with a wide range of water contents. For example, to date, with type A zeolite membranes, separation from mixtures containing organic matter with high water content is not possible; therefore, it is necessary to concentrate the organic matter to about 90% by distillation before using a type A zeolite membrane. However, in the method for manufacturing the purified component in this embodiment, even mixtures containing organic matter with, for example, a high water content of 50% or more, can have water and organic matter separated and the organic matter concentrated by using the membrane composite of this embodiment.

[0334] In the method for producing the purified component according to this embodiment, a membrane complex can be used to concentrate the organic matter to the desired concentration, or the membrane complex-based separation can be appropriately combined with other separation methods such as distillation, pressure swing adsorption (PSA), and temperature swing adsorption (TSA). By appropriately matching the conditions, the mixture can be separated with optimal energy efficiency.

[0335] In the method for manufacturing the purified component according to this embodiment, examples of organic compounds that can be separated by the membrane complex of this embodiment include: carboxylic acids such as acetic acid, propionic acid, formic acid, lactic acid, oxalic acid, tartaric acid, and benzoic acid; sulfonic acids, sulfinic acids, barbituric acid, uric acid; phenol, enols, diketone compounds, thiophenol, imides, oximes, aromatic sulfonamides, and organic acids such as primary and secondary nitro compounds. Additionally, examples of such organic compounds include: alcohols such as methanol, ethanol, and isopropanol; ketones such as acetone and methyl isobutyl ketone; aldehydes such as acetaldehyde; and diethyl acetate. Nitrogen-containing organic compounds (organic compounds containing nitrogen) such as ethers such as alkanes and tetrahydrofurans, amides such as dimethylformamide and N-methylpyrrolidone, and esters such as acetates.

[0336] The method for producing the purified component according to this embodiment exhibits significant effects in separating organic acids from mixtures of organic acids and water by utilizing both molecular sieve and hydrophilic properties. Mixtures of carboxylic acids and water are preferred, and the separation of acetic acid and water is particularly preferred. Furthermore, when separating organic matter from water in a mixture of organic matter other than organic acids, the number of carbon atoms in the organic matter is preferably 2 or more, more preferably 3 or more.

[0337] The method for producing the purified component in this embodiment can, by using the membrane composite of this embodiment, preferably by pervaporation separation, separate specific compounds from a mixture of gas or liquid containing organic matter, and further concentrate them. In practical applications, this method also exhibits sufficient throughput and sufficient separation performance. "Sufficient throughput" refers to a permeate flux of 1 kg / (m³) through the zeolite membrane. 2 •h) or above. Furthermore, "sufficient separation performance" refers to a separation coefficient of 100 or higher, commonly used in membrane separation, or a concentration of the main component in the permeate (permeate liquid) of 95% by mass or higher. The separation coefficient is expressed by the following formula. In the following formula, "Pα" represents the mass percentage concentration of the main component in the permeate liquid, "Pβ" represents the mass percentage concentration of the secondary component in the permeate liquid, "Fα" represents the mass percentage concentration of the component that is the main component in the permeate liquid within the separated mixture, and "Fβ" represents the mass percentage concentration of the component that is the secondary component in the permeate liquid within the separated mixture.

[0338] [Formula] Separation coefficient = (Pα / Pβ) / (Fα / Fβ)

[0339] [Summary of Implementation Method 2]

[0340] According to the above embodiments, the separation and concentration technology using molecular sieves enables the production of purified components requiring separation properties and acid resistance. From the viewpoint of ensuring a sustainable consumption and production model, this invention, which achieves such effects, is effective.

[0341] As can be understood from the above description, this implementation method includes the following approaches.

[0342] Method 2-1: An inorganic porous support-zeolite membrane composite (porous support-zeolite membrane composite) comprising an inorganic porous support (porous support) and a zeolite membrane supported on the surface of the inorganic porous support, wherein the intensity A (peak intensity I) of the (1,0,0) orientation in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays is... 100 The intensity B (peak intensity I) relative to the (2,0,-1) orientation 20-1 The ratio of A to B is 0.7 or more, and the molar ratio of SiO2 to Al2O3 on the surface of the zeolite film is 25 or more.

[0343] Method 2-2: The inorganic porous support-zeolite membrane composite according to Method 2-1, wherein the CF4 permeation is 1×10 -9 mol / (m 2 ·s·Pa) and below.

[0344] Method 2-3: The inorganic porous support-zeolite membrane composite according to Method 2-1 or 2-2, wherein the ratio C / D of the SiO2 / Al2O3 molar ratio C of the surface portion to the SiO2 / Al2O3 molar ratio D of the central portion in the film thickness direction of the zeolite membrane is less than 1.5.

[0345] Method 2-4: An inorganic porous support-zeolite membrane composite according to any one of methods 2-1 to 2-3, wherein the minimum thickness of the zeolite membrane is 5 μm or more.

[0346] Method 2-5: An inorganic porous support-zeolite membrane composite according to any one of methods 2-1 to 2-4, wherein the CO2 permeation is 1×10⁻⁶. -6 mol / (m 2 ·s·Pa) and below.

[0347] Method 2-6: An inorganic porous support-zeolite membrane composite according to any one of methods 2-1 to 2-5, wherein the zeolite membrane is a CHA-type zeolite crystal layer.

[0348] Method 2-7: A method for manufacturing a purified component, the method comprising: contacting a mixture of a first component of the zeolite membrane permeable to any one of methods 2-1 to 2-6 and a second component impermeable to the zeolite membrane with the inorganic porous support-zeolite membrane composite to obtain one or both of a first purified component permeable to the zeolite membrane and a second purified component impermeable to the zeolite membrane.

[0349] Method 2-8: The method for manufacturing the purified component according to Method 2-7, wherein both the first component and the second component are liquids.

[0350] Method 2-9: The method for manufacturing the purified component according to Method 2-7 or 2-8, wherein the first component and the second component are both gases.

[0351] Method 2-10: A method for manufacturing a purified component according to any one of methods 2-7 to 2-9, wherein one of the first component and the second component is water, and the other is a water-soluble organic compound.

[0352] Method 2-11: A method for manufacturing a purified component according to any one of methods 2-7 to 2-10, wherein one of the first component and the second component is water, and the other comprises an acid.

[0353] [Implementation Method 3]

[0354] Hereinafter, Embodiment 3 of the present invention will be described in detail.

[0355] [Porous Support-Zeolite Membrane Composite]

[0356] The porous support-zeolite membrane composite of this embodiment includes a porous support and a zeolite membrane formed on the porous support. This membrane composite can be achieved by appropriately combining the technical means described in Embodiments 1 and 2, within the range that the means do not conflict with each other and the effects obtained by the means are not contradictory. Examples of combined technical means include: zeolite membrane-related characteristics such as composition, surface-side SAR, central SAR, surface SAR, zeolite framework structure, zeolite membrane orientation characteristics, zeolite membrane orientation characteristics further outward than the support, zeolite membrane thickness, and zeolite particle size; porous support-related characteristics such as shape, wall thickness, average pore diameter, and porosity; and membrane composite-related characteristics such as permeation characteristics and permeation coefficient; etc., but are not limited to these. Hereinafter, an example of a membrane composite without limiting the characteristics of this embodiment will be described.

[0357] <Skeleton Structure>

[0358] In membrane complexes, from the viewpoint of adjusting the zeolite pore diameter to facilitate the diffusion of carbon dioxide within the pores and prevent hydrocarbons from easily entering them, a structure with an oxygen 6-8 member ring structure and three-dimensionally interconnected pores is preferred. The most preferred structure of the main zeolite constituting the zeolite membrane is CHA. In other words, the zeolite membrane is most preferably composed of CHA-type zeolite.

[0359] <sar>

[0360] The SiO2 / Al2O3 molar ratio of the zeolite membrane is typically 5 or more, preferably 10 or more, more preferably 15 or more, even more preferably 18 or more, particularly preferably 20 or more, even more preferably 25 or more, typically 70 or less, preferably 60 or less, and more preferably 50 or less. By setting the SiO2 / Al2O3 molar ratio of the zeolite membrane to the lower limit value or above, the acid resistance of the zeolite membrane becomes good. By setting the SiO2 / Al2O3 molar ratio of the zeolite membrane to the upper limit value or below, the hydrophilicity of the zeolite membrane becomes good, and the permeability of water and carbon dioxide becomes good.

[0361] The SiO2 / Al2O3 molar ratio at the surface of the zeolite membrane is preferably 25 or higher. Zeolite membranes exhibiting such a SAR demonstrate high acid resistance. From the viewpoint of improving acid resistance, the SAR of the surface of the zeolite membrane is typically 25 or higher, preferably 26 or higher, more preferably 27 or higher, and even more preferably 28 or higher. On the other hand, if the SAR of the zeolite membrane is too high, there is a tendency for the transmittance to decrease. From this viewpoint, the SAR of the surface of the zeolite membrane is typically 70 or lower, preferably 60 or lower, and more preferably 50 or lower.

[0362] The SAR of zeolite membranes tends to exhibit better separation characteristics with higher uniformity in the membrane thickness direction. From the viewpoint of improving separation characteristics, the ratio (SAR ratio) C / D of the SiO2 / Al2O3 molar ratio C at the surface of the zeolite membrane relative to the SiO2 / Al2O3 molar ratio D at the center in the membrane thickness direction is preferably less than 1.5, more preferably 1.4 or less, and even more preferably 1.3 or less. The lower the SAR ratio C / D is within the achievable range, the better; for example, from the viewpoint of being achievable by the manufacturing method described later, it can be 1.0 or more.

[0363] The SiO2 / Al2O3 molar ratio measured from the surface of the zeolite membrane is preferably 25 or higher. Zeolite membranes exhibiting such a SAR demonstrate high acid resistance. From the viewpoint of improving acid resistance, the SAR of the surface portion of the zeolite membrane is typically 25 or higher, preferably 26 or higher, more preferably 27 or higher, and even more preferably 28 or higher. On the other hand, if the SAR of the zeolite membrane is too high, there is a tendency for the transmittance to decrease. From this viewpoint, the SAR of the surface portion of the zeolite membrane is typically 70 or lower, preferably 60 or lower, and more preferably 50 or lower.

[0364] <Orientation Characteristics>

[0365] The peak intensity I of the (1,0,0) orientation in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays is shown in Figure 1. 100 The intensity B relative to the (2,0,-1) orientation (peak intensity I near 2θ=20.8°) 20-1 The ratio of A / B(I) 100 / I 20-1 The strength ratio A / B is preferably 0.7 or higher, more preferably 0.9 or higher, and even more preferably 1.0 or higher. Furthermore, from the viewpoint of forming a dense membrane with high permeability and high separation performance, the strength ratio A / B is preferably 100 or lower.

[0366] Furthermore, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays, the peak intensity I near 2θ=17.9° is... 111 The peak intensity I is typically around 2θ = 20.8°. 20-1 The peak intensity I is at least 0.3 times, preferably at least 0.35 times, more preferably at least 0.4 times, and typically less than 1.0 times, preferably less than 0.8 times, more preferably less than 0.7 times. 111 When the above range is met, defects in the zeolite membrane caused by thermal expansion during the manufacturing of the membrane composite, such as in the hydrothermal synthesis process, are further reduced, thus the separation performance of the membrane composite is superior.

[0367] In this embodiment, when the zeolite film is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays, the integrated intensity near 2θ=17.9° is typically 0.20 times or more, preferably 0.30 times or more, more preferably 0.40 times or more, typically less than 1.00 times, preferably less than 0.80 times, and more preferably less than 0.70 times.

[0368] When the zeolite film is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays, the integrated intensity of 2θ = 9.6° ± 0.6° is typically 1.50 times or more, preferably 2.50 times or more, more preferably 3.00 times or more, particularly preferably 3.50 times or more, most preferably 5.00 times or more, typically 10.0 times or less, preferably 9.00 times or less, more preferably 8.00 times or less, particularly preferably 7.50 times or less.

[0369] When the zeolite membrane is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the peak intensity of the peak near 2θ=17.9° is less than 0.50 times that of the peak near 2θ=20.8°, and the peak intensity of the peak near 2θ=9.6° is more than 2.0 times but less than 4.00 times that of the peak near 2θ=20.8°. The above ratio of the peak intensity of the peak near 2θ=17.9° to the peak intensity of the peak near 2θ=20.8° in the X-ray diffraction pattern when X-rays reaching the support are irradiated indicates that the zeolite crystals in the zeolite membrane are sufficiently oriented and grown, forming a dense zeolite membrane with high separation performance. From the viewpoint of forming a dense zeolite film with high separation performance, the ratio of the peak intensity of the peak near 2θ=17.9° to the peak intensity of the peak near 2θ=20.8° in the X-ray diffraction pattern when X-rays reach the support is irradiated is more preferably 0.49 or less. From the viewpoint of fully obtaining the effect of the above viewpoint, the lower limit of this ratio can be appropriately determined, for example, it can be 0.001 or more.

[0370] When the zeolite membrane is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the peak intensity of the peak near 2θ=17.9° is less than 0.50 times the peak intensity of the peak near 2θ=20.8°, and the peak intensity of the peak near 2θ=9.6° is more than 2.0 times but less than 4.00 times the peak intensity of the peak near 2θ=20.8°. From the viewpoint of forming a dense zeolite membrane with high separation performance, the lower limit of this ratio is preferably higher, and the upper limit of this ratio is preferably lower. For example, from the above viewpoint, the ratio of the peak intensity of the peak near 2θ=9.6° to the peak intensity of the peak near 2θ=20.8° in the X-ray diffraction pattern when X-rays reaching the support are irradiated is more preferably 2.10 or more, further preferably 2.30 or more, and even more preferably 2.50 or more. Furthermore, from the above viewpoint, this ratio is more preferably 3.90 or less, further preferably 3.80 or less, and even more preferably 3.70 or less.

[0371] When the zeolite membrane is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the integrated intensity of the peak near 2θ=17.9° is less than 0.50 times the integrated intensity of the peak near 2θ=20.8°, and the integrated intensity of the peak near 2θ=9.6° is more than 2.00 times but less than 8.00 times the integrated intensity of the peak near 2θ=20.8°. In the case where the zeolite membrane is composed of CHA-type zeolite, the above-mentioned ratio of the integrated intensity of the peak near 2θ=17.9° to the integrated intensity of the peak near 2θ=20.8° in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane indicates that the zeolite crystals in the zeolite membrane are sufficiently oriented and grown, forming a dense zeolite membrane with high separation performance. From the viewpoint of forming a dense zeolite membrane with high separation performance, when the zeolite membrane is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the ratio of the integrated intensity of the peak near 2θ=17.9° to the integrated intensity of the peak near 2θ=20.8° is more preferably 0.49 or less. From the viewpoint of fully obtaining the effect of the above viewpoint, the lower limit of this ratio can be appropriately determined, for example, it can be 0.001 or more.

[0372] Furthermore, in this embodiment, when the zeolite membrane is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays, the integrated intensity of the peak near 2θ=17.9° is less than 0.50 times the integrated intensity of the peak near 2θ=20.8°, and the integrated intensity of the peak near 2θ=9.6° is more than 2.00 times but less than 8.00 times the integrated intensity of the peak near 2θ=20.8°. From the viewpoint of forming a dense zeolite membrane with high separation performance, the lower limit of this ratio is preferably higher, and the upper limit is preferably lower, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite membrane with X-rays. For example, when the zeolite film is composed of CHA-type zeolite, in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays, the ratio of the integrated intensity of the peak near 2θ = 9.6° to the integrated intensity of the peak near 2θ = 20.8° is more preferably 2.1 or more, further preferably 2.3 or more, and even more preferably 2.5 or more. Furthermore, from the above viewpoint, this ratio is more preferably 7.50 or less, and even more preferably 7.00 or less.

[0373] Orientation characteristics located further outwards than the support.

[0374] In this embodiment, when X-rays are irradiated onto the surface of the zeolite film at the minimum incident angle that penetrates the zeolite film, the integrated intensity of the peak near 2θ=9.6° in the X-ray diffraction pattern can be more than 6.0 times that of the peak near 2θ=20.8°.

[0375] When X-rays are irradiated at the minimum incident angle, a high ratio of the integrated intensity of the peak near 2θ=9.6° to the integrated intensity of the peak near 2θ=20.8° in the X-ray diffraction pattern can be considered to mean, for example, that the (1,0,0) plane is oriented approximately parallel to the surface of the membrane composite when the CHA structure is set in a rhombohedral setting, thus allowing zeolite crystals to be more oriented and grow. From the viewpoint of improving the separation performance of the zeolite membrane and obtaining a dense zeolite membrane, the orientation and growth of zeolite crystals in the membrane composite is advantageous. From this viewpoint, the higher the aforementioned ratio, the better, typically 6.0 times or more, preferably 6.3 times or more, more preferably 6.5 times or more, further preferably 6.7 times or more, and particularly preferably 7.0 times or more. Among these, more preferably 10 times or more, further preferably 12 times or more, particularly preferably 15 times or more, and most preferably 20 times or more. From the viewpoint of fully obtaining the effects of the above viewpoint, the upper limit of the aforementioned ratio can be appropriately determined, for example, it can be 100 times or less.

[0376] When X-rays are irradiated at the minimum incident angle, a high ratio of the integrated intensity of the peak near 2θ=9.6° to the integrated intensity of the peak near 2θ=16.2° in the X-ray diffraction pattern can be considered to mean, for example, that the (1,0,0) plane is oriented approximately parallel to the surface of the membrane composite when the CHA structure is set in a rhombohedral setting, thus allowing zeolite crystals to be more oriented and grow. From the viewpoint of improving the separation performance of the zeolite membrane and obtaining a dense zeolite membrane, the orientation and growth of zeolite crystals in the membrane composite is advantageous. From this viewpoint, the higher the aforementioned ratio, the better; typically 6.0 times or more, preferably 6.5 times or more, more preferably 7.0 times or more, further preferably 7.5 times or more, particularly preferably 8.0 times or more, and most preferably 10.0 times or more. From the viewpoint of fully obtaining the effects described above, the upper limit of the aforementioned ratio can be appropriately determined, for example, it can be 100 times or less.

[0377] [film thickness]

[0378] The thickness of the zeolite membrane is typically 2 μm or more, preferably 3 μm or more, more preferably 5 μm or more, further preferably 7 μm or more, and particularly preferably 9 μm or more. When the zeolite membrane thickness is within this range, the membrane complex exhibits high strength and permeation selectivity, making it suitable for the separation and concentration of mixtures. There is no particular upper limit to the zeolite membrane thickness, but it is typically 30 μm or less, preferably 25 μm or less, more preferably 20 μm or less, and further preferably 15 μm or less. When the zeolite membrane thickness is within this range, in addition to the high separation performance due to sufficient membrane formation within the membrane complex, the membrane complex also exhibits high permeation flux, making it suitable for the separation and concentration of mixtures. For the separation of gas mixtures, a thickness of 5.0 μm or less is preferred, more preferably 4.0 μm or less, further preferably 3.5 μm or less, and particularly preferably 3.0 μm or less.

[0379] If the zeolite membrane is thick, the fast-reacting components in the aqueous reaction mixture will be preferentially consumed during membrane growth, thus changing the composition of the aqueous reaction mixture over time. Sometimes, the SAR (Sequential Aspect Ratio) in the thickness direction of the zeolite membrane will also change. Therefore, it is necessary to select an appropriate membrane thickness based on the structure of the target zeolite membrane.

[0380] From the viewpoint of accurately judging the uniformity of SAR of zeolite membranes, the minimum thickness of the zeolite membrane is preferably 5 μm or more. In the case of separation of gas mixtures, it is preferably 5.0 μm or less, more preferably 4.0 μm or less, even more preferably 3.5 μm or less, and particularly preferably 3.0 μm or less.

[0381] <Permeation Characteristics of Membrane Complexes>

[0382] When the measurement temperature is 50℃ and the pressure difference across the membrane is 0.3 MPa, the CF4 permeate or SF6 permeate of the membrane complex is typically 5.0 × 10⁻⁶. -9 mol / (m 2 ·s·Pa) or less, preferably 3.5×10 -9 mol / (m 2 (·s·Pa) or less, more preferably 3.0×10 -9 mol / (m 2 (·s·Pa) or less, more preferably 1.5×10 -9 mol / (m 2 ·s·Pa) or less, particularly preferably 1.0×10 -9 mol / (m 2 The optimal value is 5.0 × 10⁻⁶ (·s·Pa). -10 mol / (m 2 Below ·s·Pa). Wherein, it can be 1.0×10 -10 mol / (m 2 (·s·Pa) or less, preferably 5.0×10 -11 mol / (m 2 (·s·Pa) or less, more preferably 3.0×10 - 11 mol / (m 2 When the CF4 or SF6 permeate of the membrane complex is within this range, the defects of permeated organic compound molecules in the membrane complex are reduced, thus the separation performance of the membrane complex is better.

[0383] When the measurement temperature is 50℃ and the pressure difference across the membrane is 0.1 MPa, the CO2 permeation of the membrane complex can typically be 3.0 × 10⁻⁶. -4 mol / (m 2 Below 1.0 × 10⁻⁶ Pa. For the lower limit of CO₂ permeability of the membrane complex, for example, CO₂ permeability can be 1.0 × 10⁻⁶ Pa. -9 mol / (m 2 ·s·Pa) or above, 1.0×10 -8 mol / (m 2 (·s·Pa) or above or 1.0×10 -7 mol / (m 2 (·s·Pa) or higher. When the CO2 permeation of the membrane complex is between such upper and lower limits, the membrane complex exhibits suitable permeation flux in gas separation.

[0384] <Permeability coefficient of membrane complex>

[0385] When the zeolite constituting the zeolite membrane is a CHA-type zeolite (described later), under CF4 conditions, at a measurement temperature of 50°C and a pressure difference of 0.3 MPa across the membrane, the permeation coefficient of the membrane composite can typically be 4.5 × 10⁻⁶. -8 (mol·μm) / (m 2 ·s·Pa) or less, preferably 3.5×10 -8 (mol·μm) / (m 2 (·s·Pa) or less, more preferably 3.0×10 -8 (mol·μm) / (m 2 (·s·Pa) or less, more preferably 2.0×10 -8 (mol·μm) / (m 2 ·s·Pa) or less, particularly preferably 1.0×10 -8 (mol·μm) / (m 2 Below 5.0 × 10⁻⁶ Pa, the most preferred value is 5.0 × 10⁻⁶ Pa. -9 (mol·μm) / (m 2 ·s·Pa).

[0386] When the zeolite constituting the zeolite membrane is a CHA-type zeolite (described later), under SF6 conditions, at a measurement temperature of 50°C and a pressure difference of 0.3 MPa across the membrane, the permeation coefficient of the membrane composite can typically be 4.5 × 10⁻⁶. -8 (mol·μm) / (m 2 ·s·Pa) or less, preferably 3.5×10 -8 (mol·μm) / (m 2 (·s·Pa) or less, more preferably 3.0×10 -8 (mol·μm) / (m 2 (·s·Pa) or less, more preferably 2.0×10 -8 (mol·μm) / (m 2 ·s·Pa) or less, particularly preferably 1.0×10 -8 (mol·μm) / (m 2 Below 5.0 × 10⁻⁶ Pa, the most preferred value is 5.0 × 10⁻⁶ Pa. -9 (mol·μm) / (m 2 ·s·Pa).

[0387] When the permeation coefficient of the membrane complex falls within this range, the defects present in the membrane complex are reduced, resulting in superior separation performance. It should be noted that the values ​​mentioned above refer to the values ​​of the membrane complex synthesized in the presence of an organic template, and the values ​​of the membrane complex synthesized after removing the organic template and synthesizing it in the absence of an organic template, prior to any modifications such as ion exchange treatment or silanization.

[0388] [Manufacturing method of membrane complex]

[0389] The method for manufacturing the membrane composite according to this embodiment can be implemented by appropriately combining the operations described in Embodiments 1 and 2, respectively, according to the desired membrane composite. Therefore, the detailed description of the method for manufacturing the membrane composite according to this embodiment will not be repeated.

[0390] [Method for manufacturing purified components]

[0391] The method for manufacturing the purified component in this embodiment is as follows: a mixture of a first component that permeates through the zeolite membrane of the composite of this embodiment and a second component that does not permeate through the zeolite membrane is brought into contact with a porous support-zeolite membrane composite to obtain one or both of a first purified component that permeates through the zeolite membrane and a second purified component that does not permeate through the zeolite membrane. The operation of the method for manufacturing the purified component is as described in Embodiment 2, and therefore will not be repeated.

[0392] The method for producing the purified component can be applied to either liquids or gases. That is, both the first and second components can be liquids, or both can be gases. Furthermore, both the first and second components can be inorganic or organic substances. Additionally, the first and second components can be individual components or mixtures of two or more components. For example, one of the first and second components can be water, and the other can be a water-soluble organic compound. Furthermore, the membrane complex exhibits excellent acid resistance. Therefore, in the method for producing the purified component, one of the first and second components can be water, and the other can contain an acid. Such a method for producing the purified component can be implemented, for example, in the same manner as the separation or concentration using a membrane complex described in Patent Document 1.

[0393] [Methods for manufacturing purified organic compounds]

[0394] The method for producing purified organic compounds in this embodiment is a method for obtaining purified organic compounds from a mixture containing organic compounds using the membrane complex of this embodiment. The operation of the method for producing purified organic compounds is as described in Embodiment 1, and therefore will not be repeated.

[0395] [Additional Notes]

[0396] This invention is not limited to the embodiments described above, and various modifications can be made within the scope of the claims. Embodiments obtained by appropriately combining the technical means disclosed in different embodiments are also included within the technical scope of this invention.

[0397] Example

[0398] The following describes one embodiment of the present invention. The present invention will be described in more detail below through embodiments, but the present invention is not limited to the description of the following embodiments without departing from its spirit. In the following embodiments, the seed crystal grain size distribution, SEM-EDX measurement, X-ray diffraction (XRD) pattern measurement, grazing incidence X-ray diffraction (GIXD) measurement, gas permeation test, film thickness, air permeation, and permeation vaporization performance measurement are performed by the methods described below.

[0399] [Determination of Particle Size Distribution]

[0400] To determine the average particle size (median particle size (D50)) of the zeolite seed crystals used in the formation of the zeolite film, the particle size distribution of the zeolite seed crystals was measured under the following conditions: The average particle size of the zeolite seed crystals was defined as the cumulative 50% of the particle size (D50) in the volumetric particle size distribution determined by laser diffraction scattering.

[0401] • Device Name: Laser Diffraction Particle Size Distribution Measurement Device SALD-2100 (Manufactured by Shimadzu Corporation)

[0402] Measurement method: Laser analysis and laser scattering method

[0403] • Measurement range: 0.03~1000μm

[0404] • Light source: Semiconductor laser (wavelength 680nm, output 3mW)

[0405] • Detector: 76-element deformable concentric circle sensor, side sensor, and rear sensor (4 elements)

[0406] Sampler: SALD-BS2

[0407] • Dispersion solvent: water

[0408] [SEM-EDX Measurement]

[0409] To determine the SiO2 / Al2O3 molar ratio of zeolite seed crystals and zeolite films, SEM-EDX measurements were performed under the following conditions. The method for determining the measurement areas for SAR on the surface and central regions is as described in Embodiment 2. For the surface SAR of the zeolite film, the SiO2 / Al2O3 molar ratio at least nine points in a region of (2±0.5μm)×(2±0.5μm) was measured using three 5000x magnification surface images of the zeolite film, and the average value was taken as the surface SAR.

[0410] • Device Name (SEM): JSM-7900F (Manufactured by Nippon Electronics Co., Ltd.)

[0411] Accelerating voltage: 6kV

[0412] • Detector: Secondary electronic detector

[0413] • Device Name (EDX): Ultim Max 170 (manufactured by Oxford)

[0414] Accelerating voltage: 6kV

[0415] Multiplier: 5000x

[0416] [Determination of X-ray diffraction (XRD) patterns]

[0417] The X-ray diffraction pattern of the zeolite film surface was determined under the following conditions.

[0418] • Device Name: RIGAKU RINT-Ultima III

[0419] Optical system specifications: Incident side: 1.5kW CuX-ray tube (CuKα)

[0420] Multilayer reflector

[0421] Soller Slit (opening angle 5°)

[0422] Light-receiving side: blink counter

[0423] Long, parallel slit (opening angle 0.114°)

[0424] Measurement conditions: X-ray output (CuKα): 40kV, 30mA

[0425] Scan axis: θ / 2θ

[0426] Scan range (2θ): 5.0°~70.0°

[0427] Scanning speed: 1° / min (0.01° interval)

[0428] It should be noted that during the measurement, X-rays were irradiated in a direction parallel to the axis of the cylindrical sample.

[0429] [Grazing incidence X-ray diffraction (GIXD) determination]

[0430] In addition to controlling the incident angle of the X-rays, GIXD measurements were performed using the same method as XRD. In GIXD measurements, the incident angle of the X-rays was fixed in a single measurement, and multiple measurements were performed by changing the incident angle in each measurement, thereby controlling the incident angle of the X-rays. The incident angle of the X-rays at which the peaks originating from the zeolite film could not be detected when the incident angle was gradually decreased was set to 0°. Furthermore, the incident angle was gradually increased from 0°, and the incident angle at which the peaks of the support (alumina) began to be detected was taken as the minimum incident angle for penetrating the zeolite film, and this angle was used for zeolite film measurement.

[0431] The obtained diffraction pattern was smoothed using analysis software, Kα2 rays were removed, and peak detection was performed using the second-order differential method. For each peak, the accuracy of detection was confirmed by visual inspection, ensuring the error between the integrated intensity of the actual peak and the detection peak was within 5%. The surface height of the film was fixed by irradiating the same position on the film with X-rays while varying the irradiation angle. The integrated intensity value was obtained using the value calculated by the software for the detection peak. The peak intensity value was also obtained using the value calculated by the software for the detection peak.

[0432] [Gas Permeation Test]

[0433] Gas permeation tests were conducted to evaluate the permeation flux of the membrane complex. Figure 2 This is a schematic diagram illustrating the configuration of the apparatus used in the gas permeation test in the embodiment. Figure 2 In the apparatus, a cylindrical tubular membrane composite 21 is placed in a constant temperature bath (not shown) in a state where it is stored in a stainless steel pressure vessel 22. A temperature control unit is provided in the constant temperature bath to allow for temperature regulation of the sample gas. One end of the cylindrical tubular membrane composite 21 is sealed with a circular end pin 23. The other end is connected to one end of a connecting part 24, and the other end of the connecting part 24 is connected to the pressure vessel 22. The inner side (permeable side) of the cylindrical tubular membrane composite 21 is connected to a pipe 30 for discharging the permeated gas 28 via the connecting part 24, and the pipe 30 extends outward from the pressure vessel 22. Additionally, a pressure gauge 25 for measuring the pressure on the supply side of the supplied gas 27 and a back pressure valve 26 for adjusting the pressure on the supply side are connected at any point communicating with the pressure vessel 22. The connections between the various components are sealed.

[0434] During the separation and concentration of the mixed gas, the mixed gas (supply gas 27) is supplied at a certain supply gas pressure between the pressure vessel 22 and the membrane composite 21. The permeate gas 28 that has passed through the membrane composite 21 is measured using a flow meter (not shown) connected to the piping 30. To remove components such as moisture and air, drying above the measured temperature and exhaust gas treatment (discharge gas 29) or gas exchange treatment based on the supply gas used are performed. The sample temperature and the pressure difference between the supply gas 27 side and the permeate gas 28 side of the membrane composite 21 are kept constant. After the permeate gas flow rate stabilizes, the flow rate of the sample gas (permeate gas 28) that has passed through the membrane composite 21 is measured, and the permeate volume [mol / (m³]] is calculated. 2 The pressure used to calculate the permeation rate is the pressure difference (pressure differential) between the supply and permeation sides. The numerical expression of the result is, for example, 3.71 × 10⁻⁶ Pa. -8 The date is recorded as 3.71E-08.

[0435] [Pervaporation]

[0436] To evaluate the separation performance of the membrane complex for mixtures containing water and organic compounds, measurements based on pervaporation were performed. Figure 3 This is a schematic diagram illustrating the configuration of the apparatus used in the pervaporation process. (See diagram for example.) Figure 3 As shown, the apparatus includes: a membrane module 31 housing a porous support-zeolite membrane composite; a vacuum pump 32 connected to the membrane module 31; a glass trap 33 disposed between the membrane module 31 and the vacuum pump 32; a circulation pump 34 for conveying the mixture to the membrane module 31; temperature control units 35A and 35B disposed in the flow path of the mixture and for regulating the temperature of the mixture; and a solvent tank 36 for housing the mixture. The apparatus suitably includes valves V1 to V5. Figure 3 In the diagram, solid lines represent the flow of mixtures or water flowing into mixtures, while dashed lines represent the flow of permeate through the membrane module or the flow of vacuum.

[0437] In the pervaporation process, the mixture is first circulated in a circulation pump 34, a temperature control unit 35A, and a solvent tank 36, and the temperature is adjusted to 70°C. Next, the temperature-adjusted mixture is circulated in a membrane module 31, a solvent tank 36, and a circulation pump 34 for separation and concentration. The inner side (permeate side) of the membrane composite located within the membrane module 31 is depressurized by a vacuum pump 32, with a pressure difference of 0.4 MPaG between the inner side and the outer side (supply side) in contact with the mixture. Through this pressure difference, the permeate (mainly water) in the mixture delivered to the membrane module 31 is separated by pervaporation in the membrane composite. The permeate is captured in a glass trap 33. On the other hand, the non-permeate (mainly organic compounds) in the mixture is returned to the solvent tank 36 and concentrated, circulating within the system. Here, in the mixture returned from the membrane module 31 to the solvent tank 36, water is reduced due to separation, but this reduction is compensated by adding a predetermined amount of water at predetermined intervals via the temperature control unit 35B. After a certain period of time, the mass and concentration of the permeate collected in the glass trap 33 were measured. In this embodiment, a mixture of isopropanol (IPA) / water = 95 / 5 (mass standard) was used as the mixture. The flow rate of the mixture delivered from the circulation pump 34 to the membrane module 31 was 10 L / min, and the time from the start of circulation to the measurement was set to 30 minutes in this embodiment and 60 minutes in the comparative example.

[0438] The configuration of the apparatus used in the pervaporation process for evaluating acid resistance will be described later instead of the accompanying drawings.

[0439] [Film thickness measurement]

[0440] To determine the thickness of the zeolite membrane, a cross-section of the membrane complex was observed using scanning electron microscopy (SEM) under the following conditions. A cross-section of any portion of the zeolite membrane complex was cut out, and an image of one field of view was obtained using SEM at 2000x magnification, obtained by observing a smooth surface prepared by a cross-section polishing machine. The arithmetic mean of the distance from the surface of the zeolite membrane to the surface of the porous support was measured. At low magnification, the slope of the image was set such that the interface between the porous support and the zeolite membrane appeared horizontal to the naked eye. In the image, a line segment was drawn vertically from the surface of the zeolite membrane, and the length from the surface of the zeolite membrane to the particle that first reaches the support was measured. The width of the image was divided into four equal parts, and the measurement points were set at the center and at the left 1 / 4 and 3 / 4 positions. The arithmetic mean of the lengths measured at these three points was taken as the membrane thickness. To clarify the interface between the porous support and the zeolite membrane, the secondary electron image and the EDX image were overlaid and used for the above membrane thickness calculation.

[0441] The conditions for measuring film thickness are as follows.

[0442] • Device Name (SEM): JSM-7900F (Manufactured by Nippon Electronics Co., Ltd.)

[0443] Accelerating voltage: 6kV

[0444] • Detector: Secondary electronic detector

[0445] Multiplier: 2000x

[0446] • Device Name (EDX): Ultim Max 170 (manufactured by Oxford)

[0447] Accelerating voltage: 6kV

[0448] • Image generation and analysis software: AZtec Live (manufactured by Oxford)

[0449] Image processing software: ImageJ

[0450] [Manufacturing and characteristics of membrane complex 1]

[0451] Membrane composite 1 was fabricated as shown below.

[0452] [Loading process]

[0453] Porous alumina tubes (outer diameter 12 mm, inner diameter 9 mm, average pore diameter 1.45 μm) were used as the porous support. CHA-type zeolite seed crystals were used as the zeolite seed crystals obtained as follows: CHA-type zeolite at a weight of 2% relative to SiO2 was added as a seed crystal to a gel composition of SiO2 / Al2O3 / NaOH / KOH / H2O / N,N,N-trimethyl-1-adamantaneammonium hydroxide (TMADAOH) = 1.00 / 0.0165 / 0.120 / 0.0550 / 19.897 / 0.07, and crystallized by hydrothermal synthesis at 160 °C for 2 days. The average particle size of these zeolite seed crystals was 0.98 μm.

[0454] A porous support was immersed in a dispersion of zeolite seed crystals at 0.1% by mass in water for 1 second, followed by drying at 120°C for at least 2 hours to load the zeolite seed crystals onto the porous support. The mass of the porous support before and after loading was measured, and the loading of zeolite seed crystals was found to be 0.67 g / m³. 2 .

[0455] [Hydrothermal synthesis process]

[0456] A 25% KOH aqueous solution and a 1N-NaOH aqueous solution were added to demineralized water, and aluminum hydroxide (containing 54% by mass Al2O3, manufactured by Kyowa Chemical Co., Ltd.) was added to dissolve it, thus preparing a transparent solution. Further, an aqueous solution of N,N,N-trimethyl-1-adamantane ammonium hydroxide (hereinafter referred to as "TMADAOH") (containing 20% ​​by mass TMADAOH, manufactured by SACHEM Co., Ltd.) was added as an organic template, followed by the addition of colloidal silica (SNOWTEXST-S, manufactured by Nissan Chemical Co., Ltd.) and stirring for at least 120 minutes to prepare an aqueous reaction mixture. The composition (molar ratio) of this aqueous reaction mixture was SiO2 / Al2O3 / NaOH / KOH / H2O / TMADAOH = 1.0 / 0.064 / 0.075 / 0.15 / 100 / 0.044, and SiO2 / Al2O3 = 15.7.

[0457] The support with seed crystals attached was vertically immersed in a reaction vessel containing the above-mentioned aqueous reaction mixture. The reaction vessel was sealed and heated at 180°C under static pressure for 18 hours. At this time, the ratio of the aqueous reaction mixture to the support was approximately 2050g of aqueous reaction mixture per 1m of support, with the support in complete contact with the aqueous reaction mixture. After a given time, it was allowed to cool naturally, and then the zeolite membrane composite was removed from the aqueous reaction mixture, washed, and dried at 120°C for at least 2 hours.

[0458] (Removal process)

[0459] After drying, the membrane composite was calcined in an electric furnace at 500°C for 10 hours to remove residual organic templates from the porous support, yielding porous support-zeolite membrane composite 1 of Example 1 (membrane composite 1; the same description applies to other samples below). The heating and cooling rates during calcination were both 0.5°C / min.

[0460] The mass of the zeolite that crystallized on the porous support to form the membrane was calculated based on the difference between the mass of membrane composite 1 and the mass of the porous support. This mass was 82 g / m³. 2 .

[0461] (Characteristics of membrane complexes)

[0462] The resulting membrane composite 1 has a zeolite membrane thickness of approximately 9.4 μm. Furthermore, it was confirmed that zeolite crystals were densely formed on the surface.

[0463] The XRD pattern of the zeolite membrane of membrane composite 1 is shown in... Figure 4 The XRD pattern shows that a CHA-type zeolite film was formed. Furthermore, the intensity A (peak intensity I) of the peak near 2θ = 9.6° of this zeolite film is also analyzed. 100 The intensity B (peak intensity I) of the peak near 2θ=20.8° and the peak intensity B (peak intensity I) 20-1 ) Calculate the strength ratio A / B (I 100 / I 20-1 The result is an intensity ratio A / B of 1.52. Additionally, the peak integral intensity I near 2θ = 17.9°... 111 Peak integral intensity I near 2θ=20.8° 20-1 The peak integral intensity I near 2θ = 9.6° is 0.50. 100 Peak integral intensity I near 2θ=20.8° 20-1 The value is 2.84.

[0464] The SiO2 / Al2O3 molar ratios (SARs) of the zeolite membrane in membrane composite 1 at the surface and central portions were determined. The results showed that the SAR (C) for the surface portion was 30.8, and the SAR (D) for the central portion was 30.1. Furthermore, the ratio of these SARs, C / D, was 1.02. Additionally, the SAR for the surface portion was 28.7.

[0465] In GIXD, the incident angle of X-rays relative to the surface incident angle is set to 0.5°. The results are shown in Table 2.

[0466] The CF4 permeate of membrane composite 1 at a supply gas pressure of 0.3 MPaG is 1.5 × 10⁻⁶. -11 mol / (m 2 The CO2 permeability is 3.7 × 10⁻⁶ Pa·s. -7 mol / (m 2 The SF6 permeability is 1.5 × 10⁻⁶ Pa·s. -11 mol / (m 2 (·s·Pa). Additionally, Table 1 shows the permeate flow rates of membrane complex 1 for CO2, CH4, N2, He, H2, SF6, and CF4 at supply gas pressures of 0.1 MPaG and 0.3 MPaG. The result of pervaporation is the water permeate flow rate Q. w 2575g / (m 2 ·h), IPA transmittance Q a 2g / (m 2 ·h). Additionally, the product of Qa and film thickness is 18.8 g·μm / (m). 2 ·h).

[0467] [Manufacturing and properties of membrane complex 2]

[0468] Membrane composite 2 was fabricated as shown below.

[0469] [Loading process]

[0470] Porous alumina tubes (outer diameter 12 mm, inner diameter 9 mm, average pore diameter 1.45 μm) were used as the porous support. CHA-type zeolite seed crystals were used as the zeolite seed crystals obtained as follows: CHA-type zeolite at 2% by weight relative to SiO2 was added as a seed crystal to a gel composition of SiO2 / Al2O3 / NaOH / KOH / H2O / N,N,N-trimethyl-1-adamantaneammonium hydroxide (TMADAOH) = 1.00 / 0.033 / 0.120 / 0.0550 / 22.317 / 0.07, and crystallized by hydrothermal synthesis at 160 °C for 2 days. The average particle size of these zeolite seed crystals was 1.02 μm.

[0471] A porous support was immersed in a dispersion of zeolite seed crystals at 0.5% by mass in water for 3 minutes, followed by drying at 120°C for at least 2 hours to load the zeolite seed crystals onto the porous support. The mass of the porous support before and after loading was measured, and the loading of zeolite seed crystals was found to be 1.70 g / m³. 2 .

[0472] [Hydrothermal synthesis process]

[0473] A 25% KOH aqueous solution and a 1N-NaOH aqueous solution were added to demineralized water, and aluminum hydroxide (containing 53.5% by mass Al2O3, manufactured by Aldrich) was added to dissolve it, thus preparing a transparent solution. Further, an aqueous solution of N,N,N-trimethyl-1-adamantane ammonium hydroxide (hereinafter referred to as "TMADAOH") (containing 20% ​​by mass TMADAOH, manufactured by SACHEM) was added as an organic template, followed by the addition of colloidal silica (SNOWTEXST-S, manufactured by Nissan Chemical Co., Ltd.) and stirring for at least 120 minutes to prepare an aqueous reaction mixture. The composition (molar ratio) of this aqueous reaction mixture was SiO2 / Al2O3 / NaOH / KOH / H2O / TMADAOH = 1.0 / 0.064 / 0.075 / 0.15 / 100 / 0.044, and SiO2 / Al2O3 = 15.7.

[0474] The support with seed crystals attached was vertically immersed in a reaction vessel containing the above-mentioned aqueous reaction mixture. The reaction vessel was sealed, and the heating time to 180°C was set to 5 hours. The mixture was then heated at 180°C under static conditions and autogenous pressure for 24 hours. At this time, the ratio of the aqueous reaction mixture to the support was approximately 2050g of aqueous reaction mixture per 1m of support, with the support in complete contact with the aqueous reaction mixture. After the given time, the mixture was allowed to cool naturally. The zeolite membrane composite was then removed from the aqueous reaction mixture, washed, and dried at 120°C for at least 2 hours. The air permeation flux of the unfired membrane composite during the manufacturing process of membrane composite 2 was 0 mL / (m²). 2 ·minute).

[0475] (Removal process)

[0476] After hydrothermal synthesis, the membrane composite was allowed to cool naturally. Then, it was removed from the inner cylinder, cleaned, and dried at 120°C for at least 5 hours. After drying, the membrane composite was calcined in an electric furnace at 500°C for 10 hours to remove residual organic template from the porous support, yielding the porous support-zeolite membrane composite 2 of Comparative Example 1. The heating and cooling rates during calcination were both 0.5°C / min.

[0477] (Characteristics of membrane complexes)

[0478] The mass of the zeolite forming the membrane in the obtained membrane composite 2 was 98 g / m³. 2 Furthermore, the zeolite film thickness is 17.1 μm. Additionally, the peak intensity I near 2θ = 17.9° in the XRD pattern... 111 Peak intensity I near 2θ=20.8° 20-1 The peak intensity I near 2θ = 9.6° is 2.43. 100 Peak intensity I near 2θ=20.8° 20-1 The value is 1.46. Additionally, the peak integral intensity I near 2θ = 17.9° is... 111 Peak integral intensity I near 2θ=20.8° 20-1 The peak integral intensity I near 2θ = 9.6° is 1.04. 100 Peak integral intensity I near 2θ=20.8° 20-1 The value was 3.29. Based on the XRD pattern, it was confirmed that the zeolite film was composed of CHA-type zeolite.

[0479] In GIXD, the incident angle of X-rays relative to the surface incident angle was set to 0.6°. The results are shown in Table 2.

[0480] The SiO2 / Al2O3 molar ratios (SARs) of the zeolite membrane in membrane composite 2 were determined for the surface and central portions. The results showed that the SAR (C) for the surface portion was 19.3, and the SAR (D) for the central portion was 29.5. Furthermore, the C / D ratio of these SARs was 0.65. Additionally, the SAR for the surface portion was 20.8.

[0481] The CF4 permeate of membrane complex 2 at a gas supply pressure of 0.3 MPaG is 1.1 × 10⁻⁶. -9 mol / (m 2 The CO2 permeability is 2.8 × 10⁻⁶ Pa·s. -7 mol / (m 2 The SF6 permeability is 8.4 × 10⁻⁶ Pa·s. -10 mol / (m 2 (·s·Pa). Additionally, Table 1 shows the permeation rates of the membrane complex for CO2, CH4, N2, He, H2, SF6, and CF4 at a supply gas pressure of 0.1 MPaG. As a result of pervaporation, the water permeation rate Q... w 3471g / (m 2 ·h), IPA transmittance Q a 33g / (m 2 ·h). Additionally, the product of Qa and film thickness is 564.3 g·μm / (m). 2 ·h).

[0482] [Manufacturing and properties of membrane complex 3]

[0483] As shown below, the membrane composite 3 was manufactured in the same manner as in Example 1 of Patent Document 2.

[0484] (1) Preparation of reaction mixture for hydrothermal synthesis

[0485] A solution was prepared by adding 63.0 g of 1 mol / L KOH aqueous solution and 61.8 g of water to 2.15 g of aluminum hydroxide (containing 53.5% by mass Al2O3, manufactured by ALDRICH) and stirring until dissolved. Then, 13.5 g of colloidal silica (SNOWTEX-40, manufactured by Nissan Chemical Co., Ltd.) was added to the resulting solution and stirred for 2 hours. This prepared a reaction mixture for hydrothermal synthesis. The composition (molar ratio) of the reaction mixture was SiO2 / Al2O3 / KOH / H2O = 1 / 0.125 / 0.7 / 80. Furthermore, the SAR of this reaction mixture was 8.

[0486] (2) Preparation of inorganic porous support

[0487] The porous alumina tube (outer diameter 12mm, inner diameter 9mm) was cut into 80mm lengths, cleaned with an ultrasonic cleaner, and then dried. This prepared an inorganic porous support.

[0488] (3) Preparation of seed crystals

[0489] 10.0 g of proton-type Y-type zeolite (HY (SAR=5), manufactured by Catashoku Kasei Kogyo Co., Ltd.) was mixed with 5.00 g of NaOH and 100 g of water. The resulting mixture was heated at 100°C for 7 days, then filtered, washed with water, and dried to obtain FAU-type zeolite particles. The particle size distribution was determined, and the results showed a D50 of 1.73 μm, with maximum values ​​of 1.32 μm and 2.98 μm. Thus, the particle size was approximately 2 μm. FAU-type zeolite particles were thus prepared as seed crystals.

[0490] (4) Hydrothermal synthesis

[0491] The seed crystals were dispersed in water to prepare a 2% (w / w) aqueous dispersion. The inorganic porous support was then immersed in this dispersion for a given time. Next, the inorganic porous support was dried at 100°C for at least 5 hours. This caused the seed crystals to adhere to the outer surface of the inorganic porous support. The mass of the seed crystals adhering to the inorganic porous support was 3 g / m³. 2 .

[0492] An inorganic porous support with seed crystals attached was vertically inserted into a 200ml inner cylinder made of TEFLON (registered trademark) containing the above reaction mixture, thus immersing it in the reaction mixture. Next, the autoclave was sealed, and the temperature was raised from room temperature to 180°C over 5 hours. This temperature was then maintained at 180°C under static conditions and autogenous pressure for 24 hours, forming a zeolite film on the outer surface of the inorganic porous support. Thus, an inorganic porous support with a zeolite film, i.e., a film-forming composite, was obtained through hydrothermal synthesis.

[0493] Next, the mixture was allowed to cool naturally, and the film-forming composite was removed from the reaction mixture, washed, and dried at 100°C for 4 hours. This yielded a membrane composite 3 composed of the aforementioned zeolite membrane and inorganic porous support.

[0494] The air permeability of membrane composite 3 is 9 L / (m²). 2 ·h)(150ml / (m 2 ·minute)).

[0495] In addition, the XRD pattern of the zeolite membrane of membrane composite 3 was obtained in the same manner as in Example 1. The XRD pattern of the zeolite membrane of membrane composite 3 is shown in... Figure 6 The peak intensity I near 2θ = 9.6° in membrane complex 3 100 Peak intensity I near 2θ=20.8° 20-1 The strength ratio (A / B) is 0.67.

[0496] The strength ratio A / B of membrane composite 3 is determined to be sufficiently low compared to membrane composite 1 or 2. For the surface portion and the central portion of membrane composite 3, SAR (C, D) and their ratio C / D are not determined.

[0497] [Preparation and evaluation of membrane complex 4]

[0498] Membrane composite 4 was fabricated as shown below.

[0499] [Loading process]

[0500] Porous alumina tubes (outer diameter 12 mm, inner diameter 9 mm, average pore diameter 1.45 μm) were used as the porous support. CHA-type zeolite seed crystals were used as the zeolite seed crystals obtained as follows: CHA-type zeolite at 2% by weight relative to SiO2 was added as a seed crystal to a gel composition of SiO2 / Al2O3 / NaOH / KOH / H2O / N,N,N-trimethyl-1-adamantaneammonium hydroxide (TMADAOH) = 1.00 / 0.0165 / 0.120 / 0.0550 / 19.897 / 0.07, and crystallized by hydrothermal synthesis at 160 °C for 2 days. The average particle size of these zeolite seed crystals was 0.98 μm.

[0501] A porous support was immersed in a dispersion of zeolite seed crystals at 0.1% by mass in water for 1 second, followed by drying at 120°C for at least 2 hours to load the zeolite seed crystals onto the porous support. The mass of the porous support before and after loading was measured, and the loading of zeolite seed crystals was 0.40 g / m³. 2 .

[0502] [Hydrothermal synthesis process]

[0503] A 25% KOH aqueous solution and a 1N-NaOH aqueous solution were added to demineralized water, and aluminum hydroxide (containing 54% by mass Al2O3, manufactured by Kyowa Chemical Co., Ltd.) was added to dissolve it, thus preparing a transparent solution. Further, an aqueous solution of N,N,N-trimethyl-1-adamantane ammonium hydroxide (hereinafter referred to as "TMADAOH") (containing 20% ​​by mass TMADAOH, manufactured by SACHEM Co., Ltd.) was added as an organic template, followed by the addition of colloidal silica (SNOWTEX ST-40, manufactured by Nissan Chemical Co., Ltd.) and stirring for at least 120 minutes to prepare an aqueous reaction mixture. The composition (molar ratio) of this aqueous reaction mixture was SiO2 / Al2O3 / NaOH / KOH / H2O / TMADAOH = 1.0 / 0.048 / 0.075 / 0.15 / 100 / 0.044, and SiO2 / Al2O3 = 21.0.

[0504] The support with seed crystals attached was vertically immersed in a reaction vessel containing the above-mentioned aqueous reaction mixture. The reaction vessel was sealed and heated at 180°C under static pressure for 18 hours. At this time, the ratio of the above-mentioned aqueous reaction mixture to the above-mentioned support was approximately 2050g of aqueous reaction mixture per 1m of support, with the support being in complete contact with the above-mentioned aqueous reaction mixture. After a given time, it was allowed to cool naturally, and then the zeolite membrane composite was removed from the aqueous reaction mixture, washed, and dried at 120°C for at least 2 hours.

[0505] (Removal process)

[0506] After drying, the membrane composite was calcined in an electric furnace at 500°C for 10 hours to remove residual organic templates from the porous support, yielding the porous support-zeolite membrane composite 4 of Example 1. The heating and cooling rates during calcination were both 0.5°C / min.

[0507] (Characteristics of membrane complexes)

[0508] The mass of the zeolite that crystallized on the porous support to form the membrane was calculated based on the difference between the mass of membrane composite 4 and the mass of the porous support. This mass was 121 g / m³. 2 .

[0509] The resulting membrane composite 4 possesses a zeolite membrane thickness of 8.9 μm. Furthermore, the peak intensity I near 2θ = 17.9° in the XRD pattern... 111 Peak intensity I near 2θ=20.8° 20-1 The peak intensity I near 2θ = 9.6° is 0.49. 100 Peak intensity I near 2θ=20.8° 20-1 The value is 1.63. Additionally, the peak integral intensity I near 2θ = 17.9° is... 111 Peak integral intensity I near 2θ=20.8° 20-1 The peak integral intensity I near 2θ = 9.6° is 0.49. 100 Peak integral intensity I near 2θ=20.8° 20-1 The value was 1.92. Based on the XRD pattern, it was confirmed that the zeolite film was composed of CHA-type zeolite.

[0510] The SiO2 / Al2O3 molar ratios (SAR) of the zeolite membrane in membrane composite 4 were determined for the surface and central portions. The results showed that the SAR (C) for the surface portion was 36.2, and the SAR (D) for the central portion was 38.3. Furthermore, their SAR ratio C / D was 0.95. Additionally, the surface SAR was 34.7.

[0511] The CF4 permeate of membrane complex 4 at a supply gas pressure of 0.3 MPaG is 3.0 × 10⁻⁶. -9 mol / (m 2 The SF6 permeability is 3.4 × 10⁻⁶ Pa·s. -9 mol / (m 2 The result of pervaporation is the water permeation rate Q. w 2604g / (m 2 ·h), IPA transmittance Q a 2g / (m 2 ·h). Additionally, the product of Qa and film thickness is 17.8 g·μm / (m). 2 ·h).

[0512] [Preparation and Evaluation of Membrane Complex 5]

[0513] (1) Preparation of reaction mixture for hydrothermal synthesis

[0514] A transparent solution was prepared by adding 25.6 g of aluminum hydroxide (containing 53.9% by mass Al2O3, manufactured by Kyowa Chemical Industry Co., Ltd.) to a solution consisting of 189.5 g of 1 mol / L NaOH aqueous solution, 170.1 g of 25 wt% KOH aqueous solution and 14709 g of water, and stirring until dissolved.

[0515] An aqueous solution of N,N,N-trimethyl-1-adamantane ammonium hydroxide (hereinafter referred to as "TMADAOH") containing 20% ​​by mass TMADAOH, manufactured by SACHEM Corporation, was added to the obtained transparent solution as an organic template. Further, 1421.1 g of colloidal silica (manufactured by Nissan Chemical Co., Ltd., SNOWTEX-40) was added and the mixture was stirred for 2 hours. This yielded an aqueous reaction mixture. The composition (molar ratio) of this reaction mixture was SiO2 / Al2O3 / NaOH / KOH / H2O / TMADAOH = 1 / 0.014 / 0.02 / 0.08 / 95 / 0.04, and SiO2 / Al2O3 = 70.

[0516] (2) Preparation of inorganic porous support

[0517] Water was circulated through a porous alumina tube (outer diameter 12 mm, inner diameter 9 mm, length 1002 mm) to clean it, and then it was dried. This yielded an inorganic porous support.

[0518] (3) Preparation of seed crystals

[0519] A hydrothermal synthesis was performed at 160℃ for 2 days using a gel composition (molar ratio) of SiO2 / Al2O3 / NaOH / KOH / H2O / TMADAOH = 1 / 0.017 / 0.12 / 0.055 / 20 / 0.07. The resulting precipitate was filtered, washed with water, and dried. This yielded CHA-type zeolite particles, which were used as seed crystals. The seed crystals had a particle size of approximately 1 μm.

[0520] (4) Loading process

[0521] The seed crystal is dispersed in water. The support is then immersed in the resulting dispersion for a given time and dried at 120°C for at least 2 hours to allow the seed crystal to adhere. The increase in mass after drying relative to the mass of the support is calculated, and the amount of seed crystal adhered is determined based on the surface area of ​​the support in contact with the dispersion. The amount of seed crystal adhered is 1 g / m². 2 .

[0522] (4) Hydrothermal synthesis

[0523] A PFA inner cylinder (1200 mm in length) containing a support with seed crystals was placed inside an autoclave. The aforementioned reaction mixture was added to the inner cylinder to impregnate the support. The autoclave was then sealed and heated at 180°C under static pressure for 18 hours. After a given time, it was allowed to cool naturally. The support was then removed from the reaction mixture, cleaned, and dried at 120°C for at least 2 hours. Next, the support was fired in air at 500°C for 5 hours. The heating and cooling rates were both 0.5°C / min. This yielded a membrane composite 5 with a CHA-type zeolite film formed on the outer circumferential surface of the support.

[0524] The mass of CHA-type zeolite crystallized on the support was calculated based on the difference between the mass of membrane composite 5 and the mass of the support. The mass of CHA-type zeolite in membrane composite 5 was 32 g / m³. 2 .

[0525] (Characteristics of membrane complexes)

[0526] XRD analysis of membrane complex 5 confirmed the formation of CHA-type zeolite. The integrated intensity I of the peak near 2θ = 17.9° in the XRD was [missing value]. 111 The integrated intensity I relative to the peak near 2θ = 20.8° 20-1 The ratio is 0.4. Additionally, the integrated intensity I of the peak near 2θ = 9.6° in the XRD... 100 The integrated intensity I relative to the peak near 2θ = 20.8° 20-1 The ratio is 5.4.

[0527] The incident angle of X-rays relative to the surface incident angle in the GIXD of membrane composite 5 is 0.5°. The integrated intensity I of the peak near 2θ = 9.6° in the GIXD is... 100 The integrated intensity I relative to the peak near 2θ = 20.8° 20-1 The ratio is 7.8. Additionally, the integrated intensity I of the peak near 2θ=9.6° in GIXD... 100 The integrated intensity I relative to the peak near 2θ = 16.2° 1-11 The ratio is 14.1. The results are shown in Table 2.

[0528] The surface SAR of the zeolite membrane in membrane composite 5 is 54. Furthermore, the average thickness of the zeolite membrane in membrane composite 5 is 2.8 μm.

[0529] The CO2 permeation of membrane composite 5 at a supplied gas pressure of 0.1 MPaG and 50 °C is 1.58 × 10⁻⁶. -6 [mol·(m 2 ·s·Pa) -1 In addition, Table 1 shows the permeation rates of the membrane complex for CO2, CH4, N2, He, and H2 at a supply gas pressure of 0.3 MPaG. The ideal separation coefficient α for carbon dioxide and methane at 50 °C is 159.

[0530] [Preparation and Evaluation of Membrane Complex 6]

[0531] [Loading process]

[0532] Porous alumina tubes (outer diameter 12 mm, inner diameter 9 mm, average pore diameter 0.86 μm) were used as the porous support. CHA-type zeolite seed crystals were used as the zeolite seed crystals obtained as follows: CHA-type zeolite at a weight of 2% relative to SiO2 was added as a seed crystal to a gel composition of SiO2 / Al2O3 / NaOH / KOH / H2O / N,N,N-trimethyl-1-adamantaneammonium hydroxide (TMADAOH) = 1.00 / 0.0165 / 0.120 / 0.0550 / 19.897 / 0.07, and crystallized by hydrothermal synthesis at 160 °C for 2 days. The average particle size of these zeolite seed crystals was 0.98 μm.

[0533] A porous support was immersed in a dispersion of zeolite seed crystals at 0.1% by mass in water for 10 seconds, followed by drying at 120°C for at least 2 hours to load the zeolite seed crystals onto the porous support. The mass of the porous support before and after loading was measured, and the loading of zeolite seed crystals was found to be 1.25 g / m³. 2 .

[0534] [Hydrothermal synthesis process]

[0535] A clear solution was prepared by adding 25% KOH aqueous solution and 1N-NaOH aqueous solution to demineralized water, followed by the addition of aluminum hydroxide (containing 54% by mass Al2O3, manufactured by Kyowa Chemical Co., Ltd.) to dissolve it. Further, an aqueous solution of N,N,N-trimethyl-1-adamantane ammonium hydroxide (hereinafter referred to as "TMADAOH") (containing 20% ​​by mass TMADAOH, manufactured by SACHEM Co., Ltd.) was added as an organic template, followed by the addition of colloidal silica (SNOWTEXST-S, manufactured by Nissan Chemical Co., Ltd.) and stirring for at least 120 minutes to prepare an aqueous reaction mixture. The composition (molar ratio) of this aqueous reaction mixture was SiO2 / Al2O3 / NaOH / KOH / H2O / TMADAOH = 1.0 / 0.014 / 0.02 / 0.08 / 95 / 0.04, and SiO2 / Al2O3 = 70.0.

[0536] The support with seed crystals attached was vertically immersed in a reaction vessel containing the above-mentioned aqueous reaction mixture. The reaction vessel was sealed and heated at 180°C under static pressure for 18 hours. At this time, the ratio of the above-mentioned aqueous reaction mixture to the above-mentioned support was approximately 1680g of aqueous reaction mixture per 1m of support, with the support being in complete contact with the above-mentioned aqueous reaction mixture. After a given time, it was allowed to cool naturally, and then the zeolite membrane composite was removed from the aqueous reaction mixture, washed, and dried at 120°C for at least 2 hours.

[0537] (Removal process)

[0538] After drying, the membrane composite was calcined in an electric furnace at 500℃ for 10 hours to remove residual organic templates from the porous support, yielding a porous support-zeolite membrane composite 6. The heating and cooling rates during calcination were both 0.5℃ / min.

[0539] (Pressure treatment process)

[0540] Pressure treatment was performed using demineralized water as a solvent, and the process was repeated 30 times, with a water pressure of 10 MPaG applied for several seconds on the outside of the membrane.

[0541] Specifically, the water-sealed assembly is supplied with and pressurized by a water pressure pump (T-100K, manufactured by Kyowa). It should be noted that one end of the zeolite membrane composite is sealed with a plug, and the other end is sealed with an open top insert. The interior of the zeolite membrane composite is designed to communicate with the outside of the autoclave via the holes in the top insert (leaking), maintaining atmospheric pressure inside the support structure during pressurization.

[0542] (Characteristics of membrane complexes)

[0543] The mass of the zeolite that crystallized on the porous support to form the membrane was calculated based on the difference between the mass of membrane composite 6 and the mass of the porous support. This mass was 32.2 g / m³. 2 .

[0544] The resulting membrane composite 6 possesses a zeolite membrane thickness of 2.5 μm. Furthermore, the peak intensity I near 2θ = 17.9° in the XRD pattern... 111 Peak intensity I near 2θ=20.8° 20-1 The peak intensity I near 2θ = 9.6° is 0.44. 100 Peak intensity I near 2θ=20.8° 20-1 The value is 3.05. Additionally, the peak integral intensity I near 2θ = 17.9° is... 111 Peak integral intensity I near 2θ=20.8° 20-1 The peak integral intensity I near 2θ = 9.6° is 0.50. 100 Peak integral intensity I near 2θ=20.8° 20-1 The value was 6.35. Based on the XRD pattern, it was confirmed that the zeolite film was composed of CHA-type zeolite.

[0545] In GIXD, the incident angle of X-rays relative to the surface incident angle is 0.5°. The results are shown in Table 2.

[0546] The SAR of the surface of membrane complex 6 is 54.1.

[0547] The CF4 permeation of membrane composite 6 at a supply gas pressure of 0.1 MPaG is 2.3 × 10⁻⁶. -9 mol / (m 2 The CO2 permeability is 1.4 × 10⁻⁶ Pa·s. -6 mol / (m 2 The SF6 permeability is 1.6 × 10⁻⁶ Pa·s. -9 mol / (m 2 (·s·Pa). Additionally, Table 1 shows the permeate flow rates of membrane complex 1 for CO2, CH4, N2, He, H2, SF6, and CF4 at a supply gas pressure of 0.3 MPaG. As a result of pervaporation, the water permeate flow rate Q... w 2356g / (m 2 ·h), IPA transmittance Q a 64g / (m 2 ·h). Furthermore, the product of Qa and film thickness is 160 g·μm / (m). 2 ·h).

[0548] [Preparation and Evaluation of Membrane Complex 7]

[0549] In the hydrothermal synthesis process of membrane composite 5, the molar ratio of SiO2 / Al2O3 was set to 1:0.0077 and SiO2 / Al2O3=130. Otherwise, membrane composite 7 was manufactured by the same method.

[0550] (Characteristics of membrane complexes)

[0551] The mass of the zeolite crystallized on the porous support to form the membrane was calculated based on the difference between the mass of membrane composite 7 and the mass of the porous support. This mass was 31.9 g / m³. 2 .

[0552] The resulting membrane composite 7 possesses a zeolite membrane thickness of 3.0 μm. Furthermore, the peak intensity I near 2θ = 17.9° in the XRD pattern... 111 Peak intensity I near 2θ=20.8° 20-1 The peak intensity I near 2θ = 9.6° is 0.47. 100 Peak intensity I near 2θ=20.8° 20-1 The value is 3.56. Additionally, the peak integral intensity I near 2θ = 17.9° is... 111 Peak integral intensity I near 2θ=20.8° 20-1 The peak integral intensity I near 2θ = 9.6° is 0.41. 100 Peak integral intensity I near 2θ=20.8° 20-1 The value was 6.08. Based on the XRD pattern, it was confirmed that the zeolite film was composed of CHA-type zeolite.

[0553] The surface SAR of membrane composite 7 is 51.5.

[0554] In GIXD, the incident angle of X-rays relative to the surface incident angle was set to 0.3°. The results are shown in Table 2.

[0555] The CF4 permeation of membrane complex 7 at a supply gas pressure of 0.1 MPaG is 9.2 × 10⁻⁶. -9 mol / (m 2 (·s·Pa), CO2 permeability is 2.2×10 -6 mol / (m 2 The SF6 permeability is 8.2 × 10⁻⁶ Pa·s. -9 mol / (m 2 (·s·Pa). Additionally, Table 1 shows the permeate flow rates of membrane complex 1 for CO2, CH4, N2, He, H2, SF6, and CF4 at a supply gas pressure of 0.3 MPaG. As a result of pervaporation, the water permeate flow rate Q... w 3053g / (m 2 ·h), IPA transmittance Q a 121g / (m 2 ·h). Furthermore, the product of Qa and film thickness is 363 g·μm / (m). 2 ·h).

[0556] [Manufacturing and characteristics of membrane complex 8]

[0557] [Loading process]

[0558] Porous alumina tubes (outer diameter 12 mm, inner diameter 9 mm) were used as the porous support. CHA-type zeolite seed crystals were used as the zeolite seed crystals obtained as follows: CHA-type zeolite at a weight of 2% relative to SiO2 was added as a seed crystal to a gel composition of SiO2 / Al2O3 / NaOH / KOH / H2O / N,N,N-trimethyl-1-adamantaneammonium hydroxide (TMADAOH) = 1.00 / 0.033 / 0.1 / 0.06 / 40 / 0.07, and crystallized by hydrothermal synthesis at 160°C for 2 days. The average particle size of these zeolite seed crystals was 0.5 μm.

[0559] The porous support was impregnated in a dispersion of zeolite seed crystals and then dried at 120°C for at least 2 hours to allow the zeolite seed crystals to be loaded onto the porous support. The mass of the porous support before and after loading was measured, and the loading of zeolite seed crystals was 9.9 g / m³. 2 .

[0560] [Hydrothermal synthesis process]

[0561] A 1N-KOH aqueous solution and a 1N-NaOH aqueous solution were added to demineralized water, and aluminum hydroxide (containing 54% by mass Al2O3, manufactured by ALDRICH) was added to dissolve it, thus preparing a transparent solution. Further, an aqueous solution of N,N,N-trimethyl-1-adamantane ammonium hydroxide (hereinafter referred to as "TMADAOH") (containing 20% ​​by mass TMADAOH, manufactured by SACHEM) was added as an organic template, followed by the addition of colloidal silica (SNOWTEX ST-40, manufactured by Nissan Chemical Co., Ltd.) and stirring for at least 120 minutes to prepare an aqueous reaction mixture. The composition (molar ratio) of this aqueous reaction mixture was SiO2 / Al2O3 / NaOH / KOH / H2O / TMADAOH = 1.0 / 0.01 / 0.15 / 0.1 / 100 / 0.04, SiO2 / Al2O3 = 100.

[0562] The support with seed crystals attached was vertically immersed in a reaction vessel containing the above-mentioned aqueous reaction mixture. The reaction vessel was sealed and heated at 180°C under static pressure for 18 hours. At this time, the ratio of the above-mentioned aqueous reaction mixture to the above-mentioned support was approximately 1680g of aqueous reaction mixture per 1m of support, with the support being in complete contact with the above-mentioned aqueous reaction mixture. After a given time, it was allowed to cool naturally, and then the zeolite membrane composite was removed from the aqueous reaction mixture, washed, and dried at 120°C for at least 2 hours.

[0563] (Removal process)

[0564] After drying, the membrane composite was calcined in an electric furnace at 500°C for 10 hours to remove residual organic templates from the porous support, yielding the porous support-zeolite membrane composite 1 of Example 1. The heating and cooling rates during calcination were both 0.5°C / min.

[0565] (Characteristics of membrane complexes)

[0566] The mass of the zeolite that crystallized on the porous support to form the membrane was calculated based on the difference between the mass of membrane composite 8 and the mass of the porous support. This mass was 122 g / m³. 2 .

[0567] The resulting membrane composite 8 possesses a zeolite membrane thickness of 8.0 μm. Furthermore, the peak intensity I near 2θ = 17.9° in the XRD pattern... 111 Peak intensity I near 2θ=20.8° 20-1 The peak intensity I near 2θ = 9.6° is 0.30. 100 Peak intensity I near 2θ=20.8° 20-1 The value is 1.99. Additionally, the peak integral intensity I near 2θ = 17.9° is... 111 Peak integral intensity I near 2θ=20.8° 20-1 The peak integral intensity I near 2θ = 9.6° is 0.50. 100 Peak integral intensity I near 2θ=20.8° 20-1 The value was 3.10. Based on the XRD pattern, it was confirmed that the zeolite film was composed of CHA-type zeolite.

[0568] The SAR of the surface of membrane complex 8 is 40.2.

[0569] The incident angle of the X-rays relative to the surface in GIXD is 0.4°. The results are shown in Table 2.

[0570] The CO2 permeation of membrane complex 8 at a supplied gas pressure of 0.1 MPaG is 2.4 × 10⁻⁶. -6 mol / (m 2 (·s·Pa). In addition, the permeation rates of membrane complex 8 for CO2, CH4, N2, He, and H2 at a supply gas pressure of 0.1 MPaG are shown in Table 1.

[0571] The evaluation results of membrane complexes 1–8 are shown in Tables 1 and 2.

[0572]

[0573]

[0574] As shown in Table 1, membrane complex 1 exhibits lower CF4, SF6, and CH4 permeate rates compared to membrane complex 2. This suggests that defects in the zeolite membrane are reduced in membrane complex 1 compared to previous methods. Furthermore, membrane complex 1 shows CO2, N2, He, and H2 permeate rates to the same extent as membrane complex 2. This suggests that membrane complex 1 allows small molecules such as water to permeate to the same degree as previous methods. Based on the above, it can be concluded that membrane complex 1, due to reduced defects, makes it more difficult for larger molecules such as organic compounds to permeate, while allowing smaller molecules to permeate to the same degree as previous methods, thus exhibiting excellent separation performance.

[0575] Furthermore, a low transmittance coefficient of SF6 indicates fewer defects. That is, Qa can be considered to decrease accordingly. Considering the effect of film thickness, the product of Qa and film thickness should also decrease. Based on the above results, it is confirmed that the lower the transmittance coefficient of SF6, the smaller the product of Qa and film thickness. Therefore, it can be considered that a lower transmittance coefficient of SF6 improves selectivity.

[0576] Comparing membrane complex 1 with membrane complex 2, and membrane complex 5 with membrane complex 8, it can be seen that the peak intensity I near 2θ = 17.9° in the XRD is... 111 / I 20-1 The change has occurred; the (1,1,1) orientation has increased.

[0577] As shown in Table 2, membrane composite 1 exhibits a higher water permeation rate Q compared to membrane composite 2. w Relative to IPA permeation Q a The ratio (Q) w / Q a High-purity purified IPA was obtained. Therefore, the excellent separation performance of membrane complex 1 was confirmed. Furthermore, generally, when the content of highly permeable substances (water in the examples and comparative examples) in the fluid to be separated decreases, the partial pressure difference that drives separation decreases, thus tending to increase the permeation of low-permeability substances (IPA in the examples and comparative examples). However, for membrane complex 1, even in the low region where the content of low-permeability substances is below 5%, the permeation of highly permeable substances does not easily increase, demonstrating high separation performance.

[0578] [Evaluation of acid resistance]

[0579] For membrane composite 1 and membrane composite 2, the permeation characteristics before and after acid impregnation were calculated to evaluate the acid resistance.

[0580] Figure 7 The structure of an apparatus used in pervaporation is schematically shown. A membrane complex 5 is disposed in the liquid to be separated 4 within a container. A stir bar 3 is housed in this container, which is also placed in a hot water bath 2. Thus, the apparatus is configured to maintain the liquid to be separated 4 at a constant temperature. Furthermore, the membrane complex 5 is connected to a vacuum pump 9 via a Pirani-type vacuum gauge 6, a permeate trap 7, and a cold trap 8. In this way, the apparatus is configured to depressurize the inner surface of the membrane complex 5 to any vacuum level.

[0581] (1) Immersion in acid

[0582] Membrane composite 1 and membrane composite 2 were each immersed in an aqueous solution of approximately 2.5% by mass acetic acid at 150°C for 2 days. SEM images of the zeolite membrane surface in membrane composite 1 before acid immersion are shown below. Figure 8 SEM images of the zeolite membrane surface in membrane composite 1 before acid impregnation are shown below. Figure 9 Additionally, SEM images of the zeolite membrane surface in membrane composite 2 before acid impregnation are shown below. Figure 10 SEM images of the zeolite membrane surface in membrane composite 2 before acid impregnation are shown below. Figure 11 .

[0583] (2) Transparency test

[0584] For membrane complex 1 and membrane complex 2, separation was carried out by pervaporation before and after the above-mentioned acid impregnation, allowing water to selectively permeate from a 70°C water / 2-propanol (IPA) aqueous solution (10 / 90% by mass).

[0585] exist Figure 7 In the apparatus, the pressure difference between the outer side of the membrane composite 5 in contact with the separation liquid 4 and the inner side of the composite 5 under vacuum pressure by the vacuum pump 9 is set to approximately 1 atmosphere (1.01 × 10⁻⁶). 5 Pa) is used to cause the permeate (water) in the separated liquid 4 to permeate and vaporize, thus passing through the membrane complex 5. Based on the amount of permeate collected in the permeate trap 7, the permeation characteristics of the membrane complex 5 are determined. The results are shown in Table 1.

[0586] It should be noted that in Table 3, "Q" represents the overall permeate flux, "Qw" represents the water permeate flux, and "Qa" represents the IPA permeate flux. Additionally, Cw represents the water concentration in the permeate. The subscript "1" indicates before acid leaching, and "2" indicates after acid leaching.

[0587]

[0588] [Inspection]

[0589] As shown in Table 3, the decrease in permeation characteristics after acid impregnation is smaller for membrane composite 1 and greater for membrane composite 2. Furthermore, according to... Figures 8-11 It can be seen that in membrane composite 1, even after acid impregnation, the edge portion caused by the crystallization orientation of zeolite remains, while in membrane composite 2 after acid impregnation, this edge portion essentially disappears. It can be considered that membrane composite 1 also has high SAR on the surface of the zeolite membrane, and therefore exhibits superior acid resistance compared to membrane composite 2.

[0590] Industrial applicability

[0591] This invention can be used, for example, to separate water from mixtures of water and organic compounds such as organic solvents, i.e., aqueous organic mixtures, and to concentrate organic compounds. Additionally, this invention can be suitably used in the manufacture of purified components from aqueous components optionally containing acids, from which water has been removed.< / sar> < / sar> < / sar>

Claims

1. A porous support-zeolite membrane composite, wherein, The CF4 permeability of the porous support-zeolite membrane composite is 5.0 × 10⁻⁶. -9 mol / (m 2 Below ·s·Pa), The thickness of the zeolite membrane is less than 15 μm.

2. A porous support-zeolite membrane composite, comprising a porous support and a zeolite membrane formed on the porous support, wherein, The SF6 permeability of the porous support-zeolite membrane composite is 4.5 × 10⁻⁶. -8 mol·μm / (m 2 Below ·s·Pa), The surface SiO2 / Al2O3 molar ratio of the zeolite film is 25 or higher.

3. A porous support-zeolite membrane composite, comprising a porous support and a zeolite membrane formed on the porous support, wherein, The CF4 permeation of the porous support-zeolite membrane composite is 1.0 × 10⁻⁶. -9 mol / (m 2 Below ·s·Pa).

4. The porous support-zeolite membrane composite according to any one of claims 1 to 3, wherein, When X-rays are irradiated onto the surface of the zeolite membrane at the minimum incident angle that allows X-rays to penetrate the membrane, the integrated intensity of the peak near 2θ=9.6° in the X-ray diffraction pattern is more than 6.0 times that of the peak near 2θ=20.8°.

5. The porous support-zeolite membrane composite according to claim 1 or 3, wherein, The surface SiO2 / Al2O3 molar ratio of the zeolite membrane is 25 or higher.

6. The porous support-zeolite membrane composite according to claim 2, wherein, The thickness of the zeolite membrane is less than 15 μm.

7. The porous support-zeolite membrane composite according to claim 4, wherein, In the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays, the peak intensity I near 2θ = 17.9° is... 111 The peak intensity I is near 2θ = 20.8°. 20-1 More than 0.3 times and less than 1.0 times.

8. The porous support-zeolite membrane composite according to claim 4, wherein, The peak intensity I near 2θ = 9.6° in the X-ray diffraction pattern obtained by irradiating the surface of the zeolite film with X-rays. 100 The peak intensity I relative to 2θ = 20.8° 20-1 The ratio of I 100 / I 20-1 It is above 0.

7.

9. The porous support-zeolite membrane composite according to any one of claims 1 to 3, wherein, The ratio C / D of the SiO2 / Al2O3 molar ratio C on the surface of the zeolite film relative to the SiO2 / Al2O3 molar ratio D in the central part of the zeolite film along the film thickness direction is less than 1.

5.

10. The porous support-zeolite membrane composite according to any one of claims 1 to 3, wherein, The thickness of the zeolite membrane is 3 μm or more.

11. The porous support-zeolite membrane composite according to any one of claims 1 to 3, wherein, The minimum thickness of the zeolite membrane is 5 μm or more.

12. The porous support-zeolite membrane composite according to any one of claims 1 to 3, wherein, The zeolite membrane is composed of CHA-type zeolite.

13. A method for manufacturing a purified component, the method comprising: By contacting the porous support-zeolite membrane composite with the first component of the zeolite membrane that permeates through the porous support-zeolite membrane composite according to any one of claims 1 to 3 and the second component that does not permeate through the zeolite membrane, one or both of the first purified component that permeates through the zeolite membrane and the second purified component that does not permeate through the zeolite membrane are obtained.

14. The method for manufacturing the purified component according to claim 13, wherein, Both the first component and the second component are liquids that are miscible with each other.

15. The method for manufacturing the purified component according to claim 13, wherein, Both the first component and the second component are gases.

16. The method for manufacturing the purified component according to claim 13, wherein, One of the first component and the second component is water, and the other is a water-soluble organic compound.

17. The method for producing the purified component according to claim 13, wherein, One of the first component and the second component is water, and the other contains an acid.

18. A method for producing purified organic compounds, comprising using a porous support-zeolite membrane composite having a porous support and a zeolite membrane formed on said porous support to obtain purified organic compounds from a mixture containing organic compounds, wherein, The porous support-zeolite membrane composite is the porous support-zeolite membrane composite as described in any one of claims 1 to 3.

Citation Information

Patent Citations

  • Preparation of Molecular Sieves Using a Structure Directing Agent and An N, N, N-Triakyl Benzyl Quaternary Ammonium Cation

    US20080075656A1

  • Zeolite SSZ-13 and its method of preparation

    US4544538A

  • Inorganic porous support-zeolite membrane complex, method for producing same and separation method using same

    WO2010098473A1

  • (porous support)-(zeolite film) complex, and method for producing (porous support)-(zeolite film) complex

    WO2015159986A1